Method for producing resin composition
By setting specific pressure and temperature conditions in the mixing zone of the extruder, the cellulose fibers in the resin composition are uniformly dispersed, and the problem of insufficient mechanical properties of the resin composition in the prior art is solved, and a high-performance resin composition is realized.
Patent Information
- Application Number
- CN202280011357.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-03
- Filing Date
- 2022-02-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-02-03
AI Technical Summary
The prior art is difficult to effectively improve the tensile elongation and rigidity of resin compositions containing organic fibers such as cellulose fibers, which leads to inability to meet the requirements of high performance.
By setting a narrow gap area, a pressure reduction area or a high pressure area in the mixing area of the extruder, the first component and the second component are uniformly mixed by using complex pressure and temperature conditions to improve the mechanical properties of the resin composition.
The tensile elongation and rigidity of the resin composition are achieved, and these properties can be taken into account at a high level and stably, and are suitable for high performance applications.
Smart Images

Figure CN116867839B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a resin composition. Background Art
[0002] Thermoplastic resins are widely used in automotive parts, electrical and electronic parts, office equipment housings, precision parts and other aspects due to their light weight and excellent processing characteristics. However, the mechanical properties and dimensional stability of the resin alone are insufficient in many cases, so a composite formed by dispersing fillers in a polymer continuous phase or forming a polymer dispersed phase is usually used. As the above-mentioned filler, the use of organic fibers such as cellulose fibers has been studied in recent years. Cellulose fibers are materials with little load on the environment, have low specific gravity, and can have excellent physical property improvement effects on resin compositions, so they are expected to be fillers for environmentally friendly resin compositions. However, organic fibers such as cellulose fibers may not be easily well dispersed in polymers (resins). For example, when an extruder is used to melt-mix organic fibers and resins, depending on the mixing conditions, the expected physical property improvement effect may not be given to the resin composition. The same is true when forming a polymer alloy having a polymer continuous phase and a polymer dispersed phase. When an extruder is used to melt-mix, depending on the mixing conditions, the desired physical property improvement effect may not be obtained.
[0003] Regarding kneading of a resin composition, for example, Patent Document 1 describes a method for producing a resin composition in which, in the production of a polyamide resin composition using a twin-screw extruder, the resin pressures in a kneading zone and a full flight zone satisfy a specific relationship.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-108547 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The method described in patent documentation 1 is expected to obtain excellent molded products such as retention stability, heat aging resistance, surface appearance, but in the resin combination of filler and / or polymer dispersed phases comprising organic fibers such as cellulose fibers, no attention is paid to the method for showing the physical property improvement effect based on the filler and / or dispersed phases with the expected degree. For the resin combination comprising organic fibers such as cellulose fibers and / or polymer dispersed phases, for the favorable characteristics corresponding to its material composition (such as lightness in cellulose fibers, dimensional stability, etc.), its application in various purposes such as automotive applications has been studied. For example, in the strict purposes of the performance required by automotive applications, it is expected to take into account a plurality of characteristics (particularly tensile elongation and rigidity) and stably show these characteristics at a high level. But in the prior art, the resin combination that can form a molded body with such excellent physical property is not provided.
[0009] An object of one embodiment of the present invention is to solve the above-mentioned problems and to provide a method for producing a resin composition capable of forming a molded product having excellent tensile elongation and / or rigidity, more preferably capable of forming a molded product having both high and stable tensile elongation and rigidity.
[0010] Means for solving problems
[0011] The present disclosure includes the following aspects.
[0012] [1] A method for producing a resin composition comprising a first component and a second component, wherein:
[0013] The first component is a polymer,
[0014] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0015] The method includes a kneading step of kneading the first component and the second component using an extruder having a kneading zone including a plurality of narrow gap zones in which the gap between the inner wall of a barrel and a screw is 2 mm or less.
[0016] [2] A method as described in method 1 above, wherein the ratio [G1 / G2] of the gap [G1] in the narrowest gap zone with the smallest gap among the plurality of narrow gap zones to the average value [G2] of the gaps in narrow gap zones other than the narrowest gap zone is greater than 0.001 and less than 1.
[0017] [3] A method as described in method 1 or 2 above, wherein the ratio [G1 / G3] of the gap [G1] in the narrowest gap zone with the smallest gap among the plurality of narrow gap zones to the gaps [G3] in each narrow gap zone other than the narrowest gap zone is greater than 0.001 and less than 1.
[0018] [4] The method according to any one of the above aspects 1 to 3, wherein
[0019] The second component includes organic fiber,
[0020] The organic fibers supplied to the extruder have an average fiber length of 1 μm to 10,000 μm.
[0021] The ratio of the gap [G1] in the narrowest gap region having the smallest gap among the plurality of narrow gap regions to the average fiber length is 0.001 to 10.
[0022] [5] The method according to any one of the above aspects 1 to 4, wherein
[0023] The second component includes organic fiber,
[0024] The organic fibers supplied to the extruder are formed into pellets having an average particle size of 1 μm to 10,000 μm.
[0025] The ratio of the gap [G1] in the narrowest gap region having the smallest gap among the plurality of narrow gap regions to the average particle size is 0.001 to 10.
[0026] [6] A method as described in any one of the above methods 1 to 5, wherein the improvement rate of the bending modulus per unit mass of the mixture in each of the above multiple narrow gap regions is greater than the maximum value of the bending modulus per unit mass of the mixture in each region other than the above narrow gap region.
[0027] [7] The method according to any one of the above aspects 1 to 6, wherein
[0028] For each of the above narrow gap regions,
[0029] The pressure of the inflow into the narrow gap region is 0.5 to 20 MPa, and
[0030] The ratio of the pressure of the outflow from the narrow gap region to the pressure of the inflow into the narrow gap region is 0.2 or less.
[0031] [8] The method according to any one of the above aspects 1 to 7, wherein, for each of the narrow gap regions, the content of the second component in the inflow into the narrow gap region is 15 to 90% by mass.
[0032] [9] The method according to any one of aspects 1 to 8 above, wherein in the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through the plurality of narrow gap zones, and the mixture is cooled.
[0033]
[10] A method for producing a resin composition comprising a first component and a second component, wherein:
[0034] The first component is a polymer,
[0035] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0036] The method includes a kneading step of kneading the first component and the second component using an extruder, wherein the extruder has a kneading zone including a pressure reduction zone,
[0037] The pressure reduction zone is a portion where the pressure of the inflow into the pressure reduction zone is 0.5 to 20 MPa, and the ratio of the pressure of the outflow from the pressure reduction zone to the pressure of the inflow into the pressure reduction zone is 0.2 or less.
[0038] The content of the second component in the inflow into the pressure reduction zone is 15 to 90% by mass.
[0039]
[11] A method for producing a resin composition comprising a first component and a second component, wherein:
[0040] The first component is a polymer,
[0041] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0042] The method includes a kneading step of kneading the first component and the second component using an extruder, wherein the extruder has a kneading zone including a pressure reduction zone,
[0043] The pressure reduction zone is a portion where the pressure of the inflow into the pressure reduction zone is 0.5 to 20 MPa, and the ratio of the pressure of the outflow from the pressure reduction zone to the pressure of the inflow into the pressure reduction zone is 0.2 or less.
[0044] In the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through the pressure reduction zone, and the mixture is cooled.
[0045]
[12] A method for producing a resin composition comprising a first component and a second component, wherein:
[0046] The first component is a polymer,
[0047] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0048] The method includes a kneading step of kneading the first component and the second component using an extruder, wherein the extruder has a kneading zone including a plurality of high-pressure zones having a pressure of 0.1 MPa or more,
[0049] The pressure [P1] of the highest pressure zone with the largest pressure among the multiple high pressure zones is greater than 0.5 MPa, and the ratio [P1 / P2] of the pressure [P1] to the average value [P2] of the pressures of the high pressure zones other than the highest pressure zone is greater than 1 and less than 100.
[0050]
[13] A method as described in the above-mentioned method 12, wherein the ratio [P1 / P3] of the above-mentioned pressure [P1] to the above-mentioned pressure [P3] of each zone of the high-pressure zone other than the above-mentioned highest pressure zone is greater than 1 and is less than 100.
[0051]
[14] A method as described in method 12 or 13 above, wherein the ratio of zone length to barrel inner diameter of each of the above-mentioned multiple high-pressure zones is 1 to 30.
[0052]
[15] A method as described in any one of methods 12 to 14 above, wherein the ratio of the zone length to the inner diameter of the barrel in the above-mentioned highest pressure zone relative to the zone length to the inner diameter of the barrel in each zone in the high pressure zone other than the above-mentioned highest pressure zone is greater than 1.
[0053]
[16] A method as described in any one of methods 12 to 15 above, wherein the increase rate of the bending modulus per unit mass of the mixture in each of the above-mentioned multiple high-pressure zones is greater than the maximum value of the bending modulus per unit mass of the mixture in each zone other than the above-mentioned high-pressure zone.
[0054]
[17] The method according to any one of the above aspects 12 to 16, wherein:
[0055] For each zone in the above high pressure area,
[0056] The pressure of the inflow into the high pressure zone is 0.5 to 20 MPa, and
[0057] The ratio of the pressure of the outflow from the high-pressure region to the pressure of the inflow into the high-pressure region is 0.2 or less.
[0058]
[18] A method as described in any one of the above-mentioned methods 12 to 17, wherein, for each of the above-mentioned high-pressure zones, the content of the above-mentioned second component in the inflow into the above-mentioned high-pressure zone is 15 to 90% by mass.
[0059]
[19] A method as described in any one of the above aspects 12 to 18, wherein in the above kneading step, an additional polymer having a lower temperature than the above mixture is added to the mixture after passing through all of the above multiple high-pressure zones, and the above mixture is cooled.
[0060]
[20] A method as described in any one of the above-mentioned methods 1 to 19, wherein before the above-mentioned kneading step, it further includes a step of adding the above-mentioned second component to the melt of the above-mentioned first component to obtain a premix, and supplying the above-mentioned premix to the above-mentioned kneading zone.
[0061]
[21] A method for producing a resin composition comprising a first component and a second component, wherein:
[0062] The first component is a polymer,
[0063] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0064] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0065] The above-mentioned dispersive mixing zone comprises a first dispersive mixing zone and a second dispersive mixing zone, and the first dispersive mixing zone and the second dispersive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0066] The increment [E1] of the tensile elongation of the outflow from the first dispersing and mixing zone relative to the tensile elongation of the inflow into the first dispersing and mixing zone and the increment [E2] of the tensile elongation of the outflow from the second dispersing and mixing zone relative to the tensile elongation of the inflow into the second dispersing and mixing zone satisfy the relationship [E1]>[E2],
[0067] The increment [M1] of the bending modulus of the outflow from the first dispersed mixing zone relative to the bending modulus of the inflow into the first dispersed mixing zone and the increment [M2] of the bending modulus of the outflow from the second dispersed mixing zone relative to the bending modulus of the inflow into the second dispersed mixing zone satisfy the relationship [M1]<[M2].
[0068]
[22] A method for producing a resin composition comprising a first component and a second component, wherein:
[0069] The first component is a polymer,
[0070] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0071] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0072] In the above-mentioned dispersed mixing zone, by making one or more of the group consisting of the ratio of the zone length to the inner diameter of the barrel, the filling rate of the mixture, the temperature, the pressure and the space volume rate different in the length direction of the barrel, the travel length l (mm) of the mixture in the barrel is divided by the inner diameter d (mm) of the barrel to obtain l / d, and the ratio of the change in tensile elongation ΔE (%) per unit l / d to the change in bending modulus ΔM (GPa) per unit l / d [ΔE / ΔM] is changed in the length direction of the barrel.
[0073]
[23] A method for producing a resin composition comprising a first component and a second component, wherein:
[0074] The first component is a polymer,
[0075] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0076] The above method comprises the following steps:
[0077] A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and
[0078] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0079] The dispersive mixing zone and the distributive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0080] The increment [EA] of the tensile elongation of the outflow from the above-mentioned dispersive mixing zone relative to the tensile elongation of the inflow into the above-mentioned dispersive mixing zone and the increment [EB] of the tensile elongation of the outflow from the above-mentioned distribution mixing zone relative to the tensile elongation of the inflow into the above-mentioned distribution mixing zone satisfy the relationship [EA]>[EB],
[0081] The increment [MA] of the bending modulus of the outflow from the above-mentioned dispersed mixing zone relative to the bending modulus of the inflow into the above-mentioned dispersed mixing zone and the increment [MB] of the bending modulus of the outflow from the above-mentioned distributed mixing zone relative to the bending modulus of the inflow into the above-mentioned distributed mixing zone satisfy the relationship [MA]>[MB].
[0082]
[24] A method for producing a resin composition comprising a first component and a second component, wherein:
[0083] The first component is a polymer,
[0084] The second component is an organic fiber, a polymer different from the first component, or a combination thereof.
[0085] The above method comprises the following steps:
[0086] A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and
[0087] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0088] The concentration [CA] of the second component in the dispersed mixing zone is 10% to 90% by mass, the concentration [CB] of the second component in the distributed mixing zone is 1% to 50% by mass, and the ratio [CA] / [CB] is 2 to 90.
[0089]
[25] The method according to any one of the above aspects 1 to 20, wherein
[0090] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0091] The above-mentioned dispersive mixing zone comprises a first dispersive mixing zone and a second dispersive mixing zone, and the first dispersive mixing zone and the second dispersive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0092] The increment [E1] of the tensile elongation of the outflow from the first dispersing and mixing zone relative to the tensile elongation of the inflow into the first dispersing and mixing zone and the increment [E2] of the tensile elongation of the outflow from the second dispersing and mixing zone relative to the tensile elongation of the inflow into the second dispersing and mixing zone satisfy the relationship [E1]>[E2],
[0093] The increment [M1] of the bending modulus of the outflow from the first dispersed mixing zone relative to the bending modulus of the inflow into the first dispersed mixing zone and the increment [M2] of the bending modulus of the outflow from the second dispersed mixing zone relative to the bending modulus of the inflow into the second dispersed mixing zone satisfy the relationship [M1]<[M2].
[0094]
[26] The method according to any one of the above aspects 1 to 20, wherein
[0095] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0096] In the above-mentioned dispersed mixing zone, by making one or more of the group consisting of the ratio of the zone length to the inner diameter of the barrel, the filling rate of the mixture, the temperature, the pressure and the space volume rate different in the length direction of the barrel, the travel length l (mm) of the mixture in the barrel is divided by the inner diameter d (mm) of the barrel to obtain l / d, and the ratio [ΔE / ΔM] of the change in tensile elongation per unit l / d to the change in bending modulus ΔM (GPa) per unit l / d changes in the length direction of the barrel.
[0097]
[27] The method according to any one of the above aspects 1 to 20, wherein
[0098] The above method comprises the following steps:
[0099] A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and
[0100] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0101] The dispersive mixing zone and the distributive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0102] The increment [EA] of the tensile elongation of the outflow from the above-mentioned dispersive mixing zone relative to the tensile elongation of the inflow into the above-mentioned dispersive mixing zone and the increment [EB] of the tensile elongation of the outflow from the above-mentioned distribution mixing zone relative to the tensile elongation of the inflow into the above-mentioned distribution mixing zone satisfy the relationship [EA]>[EB],
[0103] The increment [MA] of the bending modulus of the outflow from the above-mentioned dispersed mixing zone relative to the bending modulus of the inflow into the above-mentioned dispersed mixing zone and the increment [MB] of the bending modulus of the outflow from the above-mentioned distributed mixing zone relative to the bending modulus of the inflow into the above-mentioned distributed mixing zone satisfy the relationship [MA]>[MB].
[0104]
[28] The method according to any one of the above aspects 1 to 20, wherein:
[0105] The above method comprises the following steps:
[0106] A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and
[0107] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0108] The concentration [CA] of the second component in the dispersed mixing zone is 10% to 90% by mass, the concentration [CB] of the second component in the distributed mixing zone is 1% to 50% by mass, and the ratio [CA] / [CB] is 2 to 90.
[0109]
[29] A method as described in any one of the above methods 21 to 28, wherein before the above-mentioned dispersion mixing step, it further includes a step of adding the above-mentioned second component to the melt of the above-mentioned first component to obtain a premix, and supplying the above-mentioned premix to the above-mentioned dispersion mixing zone.
[0110]
[30] The method according to any one of aspects 1 to 29 above, wherein the second component contains organic fibers.
[0111]
[31] A method as described in aspect 30 above, wherein the organic fiber is cellulose fiber.
[0112]
[32] A method as described in the above-mentioned method 30 or 31, wherein the organic fibers in the above-mentioned resin composition have an average fiber diameter of less than 1000 nm and an average fiber length / average fiber diameter ratio of more than 30.
[0113]
[33] The method according to any one of aspects 30 to 32, wherein the organic fiber is supplied to the extruder in the form of a dry body.
[0114] Effects of the Invention
[0115] According to one embodiment of the present invention, there is provided a method for producing a resin composition capable of forming a molded product having excellent tensile elongation and / or rigidity, more preferably capable of forming a molded product having both high and stable tensile elongation and rigidity. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] Figure 1 This is a diagram for explaining the steps of the method for producing a resin composition according to the first embodiment of aspect A of the present invention.
[0117] Figure 2 This is a diagram for explaining the steps of the method for producing a resin composition according to the second embodiment of aspect A of the present invention.
[0118] Figure 3This is a diagram for explaining the steps of the method for producing a resin composition according to the third embodiment of the aspect A of the present invention.
[0119] Figure 4 This is a diagram for explaining the steps of the method for producing a resin composition according to the first embodiment of aspect B of the present invention.
[0120] Figure 5 This is a diagram for explaining the changing behaviors of the tensile elongation and the flexural modulus in the method of the first embodiment of aspect B of the present invention.
[0121] Figure 6 This is a diagram for explaining the steps of the method for producing a resin composition according to the second embodiment of aspect B of the present invention.
[0122] Figure 7 This is a diagram for explaining the changing behaviors of the tensile elongation and the flexural modulus in the method of the second embodiment of aspect B of the present invention.
[0123] Figure 8 This is a diagram for explaining the steps of the method for producing a resin composition according to aspect C of the present invention. DETAILED DESCRIPTION
[0124] The following is an explanation of the embodiment of the present invention (hereinafter referred to as "the present embodiment"), but the present invention is not limited to these embodiments. In addition, unless otherwise specified, the characteristic values of the present disclosure refer to the values measured by the method described in the [Examples] of the present disclosure or the method understood by those skilled in the art to be equivalent thereto.
[0125] One embodiment of the present disclosure provides a method for manufacturing a resin composition comprising a first component and a second component. In one embodiment, the first component is a polymer, and the second component is an organic fiber, a polymer, or a combination thereof. In one embodiment, the polymer in the second component is different from the first component. In one embodiment, the first component constitutes a continuous phase in the resin composition. In one embodiment, the organic fiber that can be included in the second component is dispersed in the first component in the resin composition. In one embodiment, the polymer that can be included in the second component is present in the continuous phase of the first component in the form of a dispersed phase in the resin composition.
[0126] The method disclosed herein includes a mixing step of mixing the first component and the second component using an extruder having a mixing zone. When the first component and the second component are mixed by an extruder to manufacture a resin composition, in order to uniformly disperse the second component in the first component, it is necessary to micronize the second component itself and improve the dispersion state of the second component in the first component. In order to micronize the second component, it is necessary to apply a certain degree of strong force to the mixture, and such force may cause damage to the second component (for example, when the second component contains organic fibers, the organic fibers are broken due to bending). Therefore, the mixing conditions are preferably designed in a manner that is required for the micronization of the second component but does not impose excessive load on the second component. In the method disclosed herein, the first component and the second component are mixed in a mixing zone controlled to specific mixing conditions.
[0127] For example, in the method of aspect A described later as an embodiment exemplified in the present disclosure, a part of the region in the kneading zone is made a region where a large force is applied to the mixture.
[0128] In the method of aspect B described below as an embodiment of the present disclosure, a region for mainly improving the tensile elongation and a region for mainly improving the flexural modulus are provided in the dispersive mixing zone.
[0129] In the method of aspect C described later as an embodiment exemplified in the present disclosure, the first component and the second component are dispersedly mixed and distributedly mixed by a specific method.
[0130] It should be noted that in the present disclosure, dispersed mixing refers to a mixing form accompanied by a substantial change in the size of the second component (crushing, cutting, fiber opening, etc. of agglomerates), and distributed mixing refers to a mixing form in which the dispersion state of the second component in the first component changes, but on the other hand, the second component is not accompanied by a substantial change in the size. In one embodiment, a substantial change in size refers to a change in size of 30% or more relative to 100% of the original size in at least one dimensional index.
[0131] According to the method of one aspect of the present disclosure, the second component can be uniformly finely dispersed in the first component while avoiding damage to the second component due to the contribution of the above-mentioned unique kneading state.
[0132] In the method disclosed herein, when the first component and the second component are melt-mixed using an extruder, the second component can be melt-kneaded with the first component in the form of a dry body or a slurry (e.g., an aqueous dispersion). In a preferred embodiment, the second component is supplied to the extruder in the form of a dry body. The heating temperature throughout the entire melt-kneading process is preferably a temperature above the glass transition point of the first component but not significantly higher than the glass transition point and / or melting point.
[0133] It should be noted that in the present disclosure, the glass transition point refers to the temperature of the peak top at which the storage modulus decreases significantly and the loss modulus reaches the maximum when the temperature is increased from 23°C at a heating rate of 2°C / min and the temperature is measured at an applied frequency of 10 Hz using a dynamic viscoelasticity measuring device. When there are two or more peaks of the loss modulus, it refers to the peak top temperature of the peak on the highest temperature side. In addition, in the present disclosure, the melting point refers to the peak top temperature of the endothermic peak that appears when the temperature is increased from 23°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC). When there are two or more endothermic peaks, it refers to the peak top temperature of the endothermic peak on the highest temperature side.
[0134] The water content of the polymer subjected to melt kneading is preferably 0.2% by mass or less, or 0.1% by mass or less, or 0.07% by mass or less. From the perspective of ease of process management, the water content may be, for example, 0.001% by mass or more.
[0135] In melt kneading, a single screw extruder or a twin screw extruder can be used. In order to control the dispersibility of the second component, a twin screw extruder is preferred. The L / D of the barrel length (L) of the extruder divided by the screw diameter (D) is preferably 40 or more, particularly preferably 50 or more. In addition, the screw speed during kneading is preferably in the range of 100 to 800 rpm, more preferably in the range of 150 to 600 rpm. They vary according to the design of the screw.
[0136] Each screw in the barrel of the extruder is optimized by combining an elliptical two-blade twisted full-thread screw and a mixing element called a kneading disk. When optimizing, the screw element can have a cutout or a diversion structure. In addition, a blocking structure called a seal ring can be configured in the screw structure. As a method, the screw cross section can be composed of multiple cross sections such as 0, one, two, three, and four. In addition, these screw cross sections can also be formed into an eccentric shape.
[0137] Hereinafter, aspects A to C as exemplary embodiments of the present disclosure will be described in detail.
[0138] [Method A]
[0139] In the method of mode A, a part of the region within the kneading zone is made into a zone (also referred to as a high-load zone in the present disclosure) where a large force is applied to the mixture (more specifically, a narrow gap zone, a pressure reduction zone, or a high-pressure zone described later). By providing a high-load zone and other zones in the kneading zone, the second component can be minimised in the high-load zone (which can greatly contribute to improving the desired physical properties of the resin composition), and on the other hand, in other zones, the mixing conditions can be relaxed in such a way that the force applied to the second component is minimized to avoid damage to the second component. By using such a treatment, the second component can be uniformly microdispersed in the first component while avoiding damage to the second component, so that in one mode, a resin composition can be produced that can form a moulding body having excellent tensile elongation and / or flexural modulus, and more preferably a moulding body having both high and stable tensile elongation and flexural modulus.
[0140] More specifically, the aspect A includes the following first to third embodiments.
[0141] <<First Implementation Method>>
[0142] A first embodiment provides a method including a kneading step of kneading a first component and a second component using an extruder having a kneading zone including a plurality of narrow gap zones in which the gap between the inner wall of a barrel and a screw is 2 mm or less.
[0143] Figure 1 It is a figure explaining the process of the manufacturing method of the resin composition of the first embodiment. In the first embodiment, the extruder 100 has a kneading zone 101, and optionally can have a melting zone 102. For example, in the method of the first embodiment, before the kneading process in the kneading zone 101, it can further include a process of melting the first component a1 in the melting zone 102, adding the second component a2 to the obtained melt to obtain a premix, and the premix can be supplied to the kneading zone 101. In conventional kneading using an extruder, strong shear is applied to the mixture in the initial melting zone, so after the first component passes through the melting zone, when the second component is added to the molten first component from the addition port (side feeder), thermal degradation of the second component can be suppressed. The mixture is kneaded in the kneading zone 101 and taken out in the form of a resin composition b.
[0144] In one embodiment, the mixing zone 101 includes a plurality of narrow gap zones N1, N2, and N3 in which the gap between the inner wall of the barrel and the screw (also referred to as the barrel gap in the present disclosure) is less than 2 mm. It should be noted that in the present disclosure, the barrel gap refers to the widest flow path gap in the flow path in which the mixed mixture can flow from the upstream to the downstream of the extruder. For example, in a screw element such as a double-threaded screw, the gap in the cross section of the screw diameter direction in the direction of the minor axis is taken as the barrel gap. In addition, in a screw element such as a sealing ring, the gap between the screw and the barrel is taken as the barrel gap. Figure 1 An example in which three narrow gap zones are present is shown, but the number of narrow gap zones in the kneading zone can be selected according to the purpose, for example, it can be 2 or more or 3 or more, for example, it can be 10 or less or 5 or less.
[0145] In the plurality of narrow gap regions N1, N2, and N3, the ratio [G1 / G2] of the barrel gap [G1] (hereinafter also referred to as [G1]) of the narrowest gap region with the smallest barrel gap to the average value [G2] of the barrel gaps of the narrow gap regions other than the narrowest gap region is, in one embodiment, 0.001 or more, or 0.01 or more, or 0.1 or more, from the perspective of performing the miniaturization of the second component well, and in one embodiment, is less than 1, or 0.5 or less, or 0.3 or less, from the perspective of suppressing damage to the second component. It should be noted that the above average value [G2] refers to the barrel gap value of the region if there is one corresponding region, and refers to the arithmetic mean of the barrel gap values of the region if there are two or more corresponding regions.
[0146] Regarding the ratio [G1 / G3] of the above-mentioned [G1] to the barrel gap [G3] of each zone of the narrow gap zone other than the narrowest gap zone, from the perspective of good miniaturization of the second component, in one embodiment, it is greater than 0.001, or greater than 0.01, or greater than 0.1, and from the perspective of suppressing damage to the second component, in one embodiment, it is less than 1, or less than 0.5, or less than 0.3.
[0147] [G1] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and is preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.
[0148] [G2] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and is preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.
[0149] [G3] is preferably 0.001 mm or more, or 0.01 mm or more, or 0.05 mm or more, and is preferably 2 mm or less, or 1 mm or less, or 0.5 mm or less.
[0150] When the second component includes organic fibers, in one embodiment, the organic fibers supplied to the extruder have an average fiber length of 1 μm to 10,000 μm. It should be noted that the average fiber length disclosed herein is a value measured using a scanning electron microscope (SEM) as described below. Regarding the average fiber length, in one embodiment, it is 1 μm or more, or 10 μm or more, or 50 μm or more, and in one embodiment, it is 10,000 μm or less, or 1,000 μm or less, or 750 μm or less, or 600 μm or less. In one embodiment, regarding the ratio of the above-mentioned [G1] to the average fiber length, from the perspective of suppressing damage to the organic fibers, it is preferably 0.001 or more, or 0.01 or more, or 0.1 or more, and from the perspective of performing good miniaturization of the organic fibers, it is preferably 10 or less, or 5 or less, or 1 or less.
[0151] When the second component includes organic fibers, in one embodiment, the organic fibers supplied to the extruder form particles with an average particle size of 1 μm to 10,000 μm. The average particle size of the particles is 1 μm or more, or 10 μm or more, or 50 μm or more in one embodiment, and is 10,000 μm or less, or 1,000 μm or less, or 750 μm or less, or 500 μm or less in one embodiment. In one embodiment, the ratio of the above-mentioned [G1] to the average particle size of the particles is preferably 0.001 or more, or 0.01 or more, or 0.1 or more from the aspect of suppressing damage to the organic fibers, and is preferably 10 or less, or 5 or less, or 1 or less from the aspect of performing good miniaturization of the organic fibers.
[0152] It should be noted that the average particle size disclosed herein is a d50 particle size measured using a powder tester (for example, a powder tester manufactured by Hosokawa Micron Co., Ltd., model: PT-X).
[0153] Regarding the content of the second component that flows into each narrow gap area, from the perspective of obtaining a good property improvement effect based on the second component by containing the desired concentration of the second component in the resin composition, the above content is preferably 15 mass% or more, or 20 mass% or more, or 30 mass% or more, and from the perspective of well performing the miniaturization of the second component, it is preferably 90 mass% or less, or 80 mass% or less, or 70 mass% or less.
[0154] The pressure of the inflow into each narrow gap region is preferably 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more from the perspective of good miniaturization of the second component, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less from the perspective of suppressing damage to the second component. It should be noted that in one embodiment, the pressure of the inflow into each narrow gap region is substantially equal to the pressure of the mixed material in each narrow gap region.
[0155] The ratio of the pressure of the outflow from each narrow gap zone to the pressure of the inflow into the narrow gap zone is preferably 0.2 or less, or 0.15 or less, or 0.1 or less, from the perspective of increasing the pressure of the inflow into the narrow gap zone and being able to perform the second component finely, and preferably 0.0001 or more, or 0.001 or more, or 0.01 or more, from the perspective of suppressing the damage of the second component caused by the rapid pressure change of the mixed material. It should be noted that in one embodiment, the pressure of the outflow from each narrow gap zone is substantially equal to the pressure of the mixed material in the zone connected to each narrow gap zone on the downstream side. It should be noted that the inflow into each zone or the outflow from each zone can be a mixture flowing into or out of each zone, for example, the outflow is not limited to the case where a discharge flow path to the outside of the extruder is pre-set in the extruder structure.
[0156] The pressure of the outflow from each narrow gap zone may be 0 MPa or more, 0.001 MPa or more, or 0.01 MPa or more in one embodiment, and may be 4 MPa or less, 2 MPa or less, or 1 MPa or less in one embodiment.
[0157] Second Implementation Method
[0158] The second embodiment provides a method including a kneading step of kneading the first component and the second component using an extruder, wherein the extruder has a kneading zone including a pressure reduction zone. The method of the second embodiment has the following features, and in addition to this feature, one or more of the features exemplified above with respect to the first embodiment may be combined.
[0159] The pressure reduction zone is a portion where the pressure of the inflow into the pressure reduction zone is 0.5 to 20 MPa and the ratio of the pressure of the outflow from the pressure reduction zone to the pressure of the inflow into the pressure reduction zone is 0.2 or less.
[0160] The pressure of the inflow into the pressure reduction zone is preferably 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more from the perspective of good micronization of the second component, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less from the perspective of suppressing damage to the second component. It should be noted that in one embodiment, the pressure of the inflow into the pressure reduction zone is substantially equal to the pressure of the mixed material in the pressure reduction zone.
[0161] In one embodiment, the content of the second component in the inflow into the pressure reduction zone is 15 to 90 mass %, and / or in the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through the pressure reduction zone, and the mixture is cooled.
[0162] In a specific embodiment, the content of the second component of the influent flowing into the pressure reduction zone is 15 to 90% by mass, the pressure of the influent flowing into the pressure reduction zone is 0.5 to 20 MPa, and the ratio of the pressure of the outflow from the pressure reduction zone to the pressure of the influent flowing into the pressure reduction zone is less than 0.2.
[0163] In a specific embodiment, the pressure of the influent flowing into the pressure reduction zone is 0.5 to 20 MPa, the ratio of the pressure of the outflow flowing out of the pressure reduction zone to the pressure of the influent flowing into the pressure reduction zone is less than 0.2, and in the kneading process, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through the pressure reduction zone, and the mixture is cooled.
[0164] Reference Figure 2 In the second embodiment, the extruder 200 has a kneading zone 201 and may optionally have a melting zone 202. For example, in the method of the second embodiment, before the kneading step in the kneading zone 201, the process of melting the first component a1 in the melting zone 202 and adding the second component a2 to the obtained melt to obtain a premix may be further included, and the premix may be supplied to the kneading zone 201. In conventional kneading using an extruder, a strong shear is applied to the mixture in the initial melting zone, so after the resin as the first component passes through the melting zone, when the second component is added to the molten resin from the addition port (side feeder), thermal degradation of the second component can be suppressed. The mixture is kneaded in the kneading zone 201 and taken out in the form of a resin composition b.
[0165] The kneading zone 201 in the second embodiment includes a pressure reduction zone D1. Figure 2An example in which there is one pressure reduction zone D1 is shown, but in the second embodiment, the number of pressure reduction zones can be selected according to the purpose, and in one embodiment it is 1 or more, or 2 or more, or 3 or more, and in one embodiment it is 10 or less, or 5 or less.
[0166] The pressure reduction zone in the second embodiment may be the narrow gap zone described in the first embodiment in one embodiment. The barrel gap in the narrow gap zone may be the same as that illustrated in the first embodiment. The pressure reduction zone may be formed by adjusting one or more of the group consisting of the zone length / barrel inner diameter ratio, the mixture filling rate, the temperature, the pressure, the screw speed, the feed rate, the resin composition, and the space volume rate disclosed in the present invention.
[0167] 《Third Implementation Mode》
[0168] Figure 3 This is a diagram for explaining the steps of the method for producing a resin composition according to the third embodiment. The method according to the third embodiment has the following features, and in addition to these features, one or more of the features exemplified above for the first or second embodiment may be combined.
[0169] Reference Figure 3 In the third embodiment, the extruder 300 has a kneading zone 301 and may optionally have a melting zone 302. For example, in the method of the third embodiment, before the kneading step in the kneading zone 301, the first component a1 may be further melted in the melting zone 202 and the second component a2 may be added to the obtained melt by, for example, side feeding to obtain a premix, and the premix may be supplied to the kneading zone 301. From the perspective of suppressing thermal degradation of the second component, such an addition method is preferred. The mixture is kneaded in the kneading zone 301 and taken out in the form of a resin composition b.
[0170] In one embodiment, the kneading zone 301 includes a plurality of high pressure zones H1 , H2 , and H3 , each having a pressure of 0.1 MPa or more. Figure 3 An example in which three high pressure zones are present is shown, but the number of high pressure zones in the kneading zone can be selected according to the purpose, for example, it can be 2 or more, or 3 or more, for example, it can be 10 or less, or 5 or less.
[0171] The ratio [P1 / P2] of the pressure [P1] (hereinafter also referred to as [P1]) of the highest pressure region with the largest pressure among the plurality of high pressure regions H1, H2, and H3 to the average value [P2] of the pressures of the high pressure regions other than the highest pressure region is greater than 1, or 1.5 or more, or 2 or more in one embodiment from the perspective of good miniaturization of the second component, and is 100 or less, or 50 or less, or 20 or less in one embodiment from the perspective of suppressing damage to the second component. It should be noted that the above average value [P2] refers to the pressure value of the region if there is one corresponding region, and refers to the arithmetic average of the pressure values of the regions if there are two or more corresponding regions.
[0172] Regarding the ratio [P1 / P3] of the pressure [P3] of each zone of the high-pressure zone other than the highest pressure zone [P1], from the perspective of good miniaturization of the second component, in one embodiment, it is greater than 1, or is greater than 1.5, or is greater than 2, and from the perspective of suppressing damage to the second component, in one embodiment, it is less than 100, or less than 50, or less than 20.
[0173] [P1] In one embodiment, it is 0.5 MPa or more, preferably 1 MPa or more, or 2 MPa or more, and preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.
[0174] [P2] is preferably 0.1 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.
[0175] [P3] is preferably 0.1 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, and is preferably 20 MPa or less, or 15 MPa or less, or 10 MPa or less.
[0176] Regarding the zone length / barrel inner diameter ratio of each of the multiple high-pressure zones, from the perspective of successfully performing the miniaturization of the second component, in one embodiment, it is greater than 1, or greater than 2, or greater than 4; from the perspective of suppressing damage to the second component, in one embodiment, it is less than 30, or less than 20, or less than 15.
[0177] Regarding the ratio of the zone length / barrel inner diameter ratio of the highest pressure zone to the zone length / barrel inner diameter ratio of each zone in the high pressure zone other than the highest pressure zone, from the perspective of good miniaturization of the second component, in one embodiment, it is greater than 1, or greater than 2, or greater than 4, and from the perspective of suppressing damage to the second component, in one embodiment, it is less than 30, or less than 20, or less than 15.
[0178] Regarding the pressure in the highest pressure zone, from the perspective of successfully performing the miniaturization of the second component, in one embodiment, it is greater than 0.3 MPa, or greater than 0.5 MPa, or greater than 1 MPa, and from the perspective of suppressing damage to the second component, in one embodiment, it is less than 50 MPa, or less than 20 MPa, or less than 15 MPa.
[0179] Other Districts
[0180] Reference Figures 1 to 3 , the kneading zones 101, 201, 301 may have a dispersive mixing zone and a distributive mixing zone. The narrow gap zones N1, N2, N3, the pressure reduction zone D1, and the high pressure zones H1, H2, H3 are dispersive mixing zones. On the other hand, each of the other zones 11, 12, 13, 14, 21, 22, 31, 32, 33, 34 may be a dispersive mixing zone or a distributive mixing zone. The kneading conditions of the other zones may be arbitrarily designed to be the same or different from each other as needed. In a preferred embodiment, the most downstream zone of the kneading zone is the other zone (e.g. Figures 1 to 3 The other zones 14, 22, 24) are preferably distribution mixing zones.
[0181] 《Addition of additional polymers》
[0182] Reference Figures 1 to 3 In the method of mode A, an additional polymer of the same or different type, preferably the same type, as the polymer in the mixture may be added to the mixture in the kneading zones 101, 201, 301 (e.g., side feed). In a representative mode, the additional polymer may be added to the downstream side of all the narrow gap zones N1, N2, N3 of the kneading zone 101, the downstream side of the pressure reduction zone D1 of the kneading zone 201, or the downstream side of all the high pressure zones H1, H2, H3 of the kneading zone 301.
[0183] The amount of the additional polymer added can be determined according to the kneading conditions, the desired concentration of the second component of the resin composition, etc., and for example, it can be 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more, and can be 1000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less, based on 100 parts by mass of the mixture. In one embodiment, the concentration of the second component of the mixture before adding the additional polymer can be 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 25% by mass or more, or 30% by mass or more, and / or 90% by mass or less, or 80% by mass or less, or 70% by mass or less, or 60% by mass or less, or 50% by mass or less, and the concentration of the second component of the mixture after adding the additional polymer (in one embodiment, the same as the concentration of the second component in the resin composition) can be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 5% by mass or more, and / or 50% by mass or less, or 40% by mass or less, or 30% by mass or less, or 20% by mass or less.
[0184] (Based on cooling with additional polymer)
[0185] The additional polymer may be lower in temperature than the mixture. That is, in the kneading process, an additional polymer having a lower temperature than the mixture may be added to the mixture after passing through all of the plurality of narrow gap zones of the first embodiment, or the pressure reduction zones of the second embodiment (if there are a plurality of them, in one embodiment, all of them), or all of the plurality of high pressure zones of the third embodiment, and the mixture may be cooled. The temperature of the additional polymer added for cooling is, in one embodiment, 0°C or higher, or 10°C or higher, or 20°C or higher, and in one embodiment, 300°C or lower, or 200°C or lower, or 100°C or lower, or 50°C or lower. The temperature of the mixture to which the additional polymer is added is, in one embodiment, 100°C or higher, or 150°C or higher, or 200°C or higher, and in one embodiment, 450°C or lower, or 400°C or lower, or 350°C or lower.
[0186] 《Changes in flexural modulus》
[0187] In the method of embodiment A, the bending modulus improvement rate per unit mass of the mixture in each of the plurality of high-load zones (i.e., the ratio of the bending modulus of the outflow from each zone to the bending modulus of the inflow into each zone) can be greater than the maximum value of the bending modulus improvement rate per unit mass of the mixture in each zone other than the high-load zone (i.e., the ratio of the bending modulus of the outflow from each zone to the bending modulus of the inflow into each zone). In this case, the bending modulus improvement effect of each high-load zone is good, while damage to the second component can be suppressed in other zones.
[0188] 《Changes in Thixotropic Index》
[0189] In the method of form A, the ratio of the thixotropic index of the outflow from the kneading zone to the thixotropic index of the inflow into the kneading zone is preferably 1 or more, or 2 or more, or 3 or more from the aspect of uniform fine dispersion of the second component in the kneading zone, and is preferably 100 or less, or 50 or less, or 10 or less from the aspect of suppressing damage to the second component.
[0190] [Method B]
[0191] The method of the embodiment B of the present disclosure includes a dispersive mixing step of dispersing and mixing the first component and the second component in the dispersive mixing zone of the extruder. The method of embodiment B has the following features, and in addition to the features, one or more of the features exemplified above with respect to embodiment A may be combined. In one embodiment, the dispersive mixing zone of embodiment B may have a high load zone (more specifically, a narrow gap zone, a pressure reduction zone, or a high pressure zone) of embodiment A.
[0192] [1] A method for producing a resin composition comprising a first component and a second component, wherein:
[0193] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0194] The above-mentioned dispersive mixing zone comprises a first dispersive mixing zone and a second dispersive mixing zone, and the first dispersive mixing zone and the second dispersive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0195] The increment [E1] of the tensile elongation of the outflow from the first dispersing and mixing zone relative to the tensile elongation of the inflow into the first dispersing and mixing zone and the increment [E2] of the tensile elongation of the outflow from the second dispersing and mixing zone relative to the tensile elongation of the inflow into the second dispersing and mixing zone satisfy the relationship [E1]>[E2],
[0196] The increment [M1] of the bending modulus of the outflow from the first dispersed mixing zone relative to the bending modulus of the inflow into the first dispersed mixing zone and the increment [M2] of the bending modulus of the outflow from the second dispersed mixing zone relative to the bending modulus of the inflow into the second dispersed mixing zone satisfy the relationship [M1]<[M2].
[0197] [2] A method as described in the above-mentioned embodiment 1, wherein the first dispersive mixing zone and the second dispersive mixing zone are directly connected in a manner such that the first dispersive mixing zone is on the upstream side.
[0198] [3] A method as described in the above-mentioned embodiment 1, wherein the first dispersive mixing zone and the second dispersive mixing zone are directly connected in a manner such that the second dispersive mixing zone is on the upstream side.
[0199] [4] The method according to any one of the above aspects 1 to 3, wherein
[0200] The second component includes organic fibers, and the mass ratio of the organic fibers having a fiber diameter of 50 μm or more in the inflow into the first dispersing and mixing zone is 10% to 90%.
[0201] The ratio (1b / 1a) of the mass ratio (1b) of the organic fibers having a fiber diameter of 50 μm or more in the outflow from the first dispersing and mixing zone to the mass ratio (1a) of the organic fibers having a fiber diameter of 50 μm or more in the inflow into the first dispersing and mixing zone is 0 to 0.6,
[0202] The ratio (2b / 2a) of the mass proportion (2b) of the component with a fiber diameter of 50 μm or more in the organic fibers in the outflow from the above-mentioned second dispersion mixing zone to the mass proportion (2a) of the component with a fiber diameter of 50 μm or more in the organic fibers in the inflow into the above-mentioned second dispersion mixing zone is 0.6 to 1.
[0203] [5] A method as described in any one of the above methods 1 to 4, wherein the above [E1] is 1% to 100%, the above [E2] is 0% to 10%, the above [M1] is 0 GPa to 1 GPa, the above [M2] is 0.1 GPa to 20 GPa, the absolute value of the difference between the above [E1] and [E2] is 0.1% to 100%, and the absolute value of the difference between the above [M1] and [M2] is 0.1 GPa to 20 GPa.
[0204] [6] A method as described in any one of the above-mentioned methods 1 to 5, wherein the ratio of the zone length to the barrel inner diameter of each of the above-mentioned first dispersing and mixing zone and the above-mentioned second dispersing and mixing zone is 1 to 30.
[0205] [7] A method as described in any one of the above-mentioned aspects 1 to 6, wherein the mixture filling rate of each of the above-mentioned first dispersive mixing zone and the above-mentioned second dispersive mixing zone is 10% to 100%.
[0206] [8] The method according to any one of the above-mentioned aspects 1 to 7, wherein the temperature of each of the first dispersing and mixing zone and the second dispersing and mixing zone is 100°C to 400°C.
[0207] [9] A method as described in any one of the above-mentioned methods 1 to 8, wherein the pressure of the mixed material in each of the above-mentioned first dispersive mixing zone and the above-mentioned second dispersive mixing zone is 0 MPa to 15 MPa.
[0208]
[10] A method for producing a resin composition comprising a first component and a second component, wherein:
[0209] The method comprises a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder,
[0210] In the above-mentioned dispersed mixing zone, by making one or more of the group consisting of the ratio of the zone length to the inner diameter of the barrel, the filling rate of the mixture, the temperature, the pressure and the space volume rate different in the length direction of the barrel, the travel length l (mm) of the mixture in the barrel is divided by the inner diameter d (mm) of the barrel to obtain l / d, and the ratio of the change in tensile elongation ΔE (%) per unit l / d to the change in bending modulus ΔM (GPa) per unit l / d [ΔE / ΔM] is changed in the length direction of the barrel.
[0211]
[11] A method as described in aspect 10 above, wherein the ratio [ΔE / ΔM] is gradually decreased from the upstream side to the downstream side of the barrel.
[0212]
[12] A method as described in aspect 10 above, wherein the ratio [ΔE / ΔM] is gradually increased from the upstream side to the downstream side of the barrel.
[0213]
[13] A method as described in any one of the above methods 1 to 12, wherein the above-mentioned second component contains organic fibers, preferably cellulose fibers, and the organic fibers in the above-mentioned resin composition have an average fiber diameter of less than 1000 nm and an average fiber length / average fiber diameter ratio of more than 30.
[0214]
[14] A method as described in any one of the above methods 1 to 13, wherein before the above dispersion mixing step, it further includes a step of adding the above second component to the melt of the above first component to obtain a premix, and supplying the above premix to the above dispersion mixing zone.
[0215] In the method of form B, a region that mainly improves the tensile elongation (also referred to as the tensile elongation improvement region in the present disclosure) and a region that mainly improves the flexural modulus (also referred to as the flexural modulus improvement region in the present disclosure) are provided in the dispersive mixing region. In the tensile elongation improvement region, the coarse aggregates of the second component are crushed, thereby improving the tensile elongation of the mixture, while on the other hand, the crushing of the coarse aggregates contributes little to improving the flexural modulus (i.e., rigidity) of the mixture. On the other hand, in the flexural modulus improvement region, the second component is microdispersed in the first component, thereby improving the flexural modulus of the mixture, while on the other hand, the microdispersion contributes little to improving the tensile elongation of the mixture.
[0216] In the method of mode B, the tensile elongation and the flexural modulus are not increased at the same time, but one of the tensile elongation and the flexural modulus is increased in each region of the tensile elongation improvement region and the flexural modulus improvement region. According to the resin composition obtained by such treatment, unexpectedly, compared with the resin composition obtained by the treatment in which the tensile elongation and the flexural modulus are increased at the same time, the tensile elongation and the flexural modulus can be taken into account at a high level and stably. The above advantages can become significant when the second component contains organic fibers, especially cellulose fibers.
[0217] Mode B more specifically includes the following first and second embodiments.
[0218] <<First Implementation Method>>
[0219] Figure 4 It is a figure explaining the process of the manufacturing method of the resin composition of 1st Embodiment, Figure 5 This is a diagram for explaining the changing behaviors of tensile elongation and flexural modulus in the method of the first embodiment. Figure 4 In the first embodiment, the extruder 400 has a dispersive mixing zone 401. The extruder 400 may further have a distributive mixing zone 402. The extruder 400 may further have a melting zone 403 upstream of the dispersive mixing zone 401 and / or a melting zone 404 downstream of the dispersive mixing zone 401. For example, the method of the present disclosure may further include a step of melting the first component a1 in the melting zone 403 and adding the second component a2 to the obtained melt to obtain a premix before the dispersive mixing step in the dispersive mixing zone 401, and the premix may be supplied to the dispersive mixing zone 401. In conventional mixing using an extruder, a strong shear is applied to the mixture in the initial melting zone, so when the second component is added to the first component in a molten state from the addition port (side feeder) after the resin passes through the melting zone, thermal degradation of the second component can be suppressed. The mixture is dispersedly mixed and optionally distributedly mixed in the extruder 400 and taken out in the form of a resin composition b.
[0220] In addition, in the method of embodiment B, after the dispersion mixing step and before the distribution mixing step, a step of adding an additional polymer of the same or different type, preferably the same type as the first component in the dispersion mixing product to obtain an additional polymer mixture is further included, and the additional polymer mixture can be supplied to the distribution mixing zone. For example, the additional polymer can be added to the effluent flowing out of the dispersion mixing zone 401 (for example, by Figure 4 After the additional polymer is fed to the melting zone 404 (side feeding of the additional polymer), it is supplied to the distribution mixing zone 402. The amount of the additional polymer added can be determined according to the kneading conditions, the desired concentration of the second component of the resin composition, etc., for example, it can be 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more relative to 100 parts by mass of the dispersed mixed product, and can be 1000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less. In one embodiment, the concentration of the second component of the dispersed mixed product can be greater than 10% by mass, or greater than 20% by mass, or greater than 25% by mass, or greater than 30% by mass, and / or less than 80% by mass, or less than 70% by mass, or less than 60% by mass, or less than 50% by mass, and the concentration of the second component of the additional polymer mixture (which is equal to the concentration of the second component in the resin composition in one embodiment) can be greater than 1% by mass, or greater than 2% by mass, or greater than 3% by mass, or greater than 5% by mass, and / or less than 50% by mass, or less than 40% by mass, or less than 30% by mass, or less than 20% by mass.
[0221] (Based on cooling with additional polymer)
[0222] The additional polymer may have a lower temperature than the dispersed mixed product, thereby cooling the dispersed mixed product. The temperature of the additional polymer added for cooling is, in one embodiment, 0°C or more, or 10°C or more, or 20°C or more, and in one embodiment, 300°C or less, or 200°C or less, or 100°C or less, or 50°C or less. The temperature of the dispersed mixed product to which the additional polymer is added is, in one embodiment, 100°C or more, or 150°C or more, or 200°C or more, and in one embodiment, 450°C or less, or 400°C or less, or 350°C or less.
[0223] The dispersion mixing zone 401 includes a first dispersion mixing zone 41 and a second dispersion mixing zone 42 having different processing conditions. In one embodiment, the first dispersion mixing zone 41 and the second dispersion mixing zone 42 are directly connected to each other. In one embodiment, an additional dispersion mixing zone may exist upstream of the first dispersion mixing zone 41, between the first dispersion mixing zone 41 and the second dispersion mixing zone 42, and / or downstream of the second dispersion mixing zone 42. For example, the following structure can be illustrated: a third dispersion mixing zone (not shown) having the same or different structure as the first dispersion mixing zone 41 or the second dispersion mixing zone 42 is arranged downstream of the second dispersion mixing zone 42, and the effluent flowing out of the third dispersion mixing zone is recovered in the form of a resin composition b.
[0224] In one embodiment, the processing conditions are one or more selected from the group consisting of a zone length / barrel inner diameter ratio, a mixture filling rate, a temperature, a pressure, and a space volume ratio.
[0225] The zone lengths noted above are the combined lengths of the screw elements that make up the dispersive mixing zone and the distributive mixing zone and depend on the screw configuration.
[0226] The mixture filling rate is the ratio of the actual filling amount (volume basis) of the mixture to the spatial volume of the extruder. After the rotation of the screw and the supply of raw materials are suddenly stopped, the screw is pulled out, and the mixture attached to the screw surface is collected and measured, and the volume filled with the mixture is divided by the density of the mixture to calculate the volume, and then the volume filled with the mixture is divided by the spatial volume described below to calculate the mixture filling rate. The mixture filling rate depends on the screw structure and extrusion conditions.
[0227] The above-mentioned space volume ratio is calculated by subtracting the screw volume (the sum of the element volume and the shaft volume) from the barrel volume of the extruder to calculate the space volume, and dividing the space volume by the barrel volume. The space volume ratio depends on the screw structure.
[0228] Reference Figure 4 and Figure 5, the increment [E1] of the tensile elongation of the outflow 41b flowing out of the first dispersed mixing zone relative to the tensile elongation of the inflow 41a flowing into the first dispersed mixing zone and the increment [E2] of the tensile elongation of the outflow 42b flowing out of the second dispersed mixing zone relative to the tensile elongation of the inflow 42a flowing into the second dispersed mixing zone satisfy the relationship [E1]>[E2]. In addition, the increment [M1] of the bending modulus of the outflow 41b flowing out of the first dispersed mixing zone relative to the bending modulus of the inflow 41a flowing into the first dispersed mixing zone and the increment [M2] of the bending modulus of the outflow 42b flowing out of the second dispersed mixing zone relative to the bending modulus of the inflow 42a flowing into the second dispersed mixing zone satisfy the relationship [M1]<[M2]. That is, the first dispersed mixing zone is a zone where the tensile elongation is improved, and the second dispersed mixing zone is a zone where the bending modulus is improved.
[0229] In one approach, Figure 4 As shown, the first dispersive mixing zone 41 and the second dispersive mixing zone 42 are connected (directly connected in one embodiment) with the first dispersive mixing zone 41 being on the upstream side. Such an arrangement is advantageous in further improving the elastic modulus.
[0230] On the other hand, in another embodiment, the first and second dispersive mixing zones may be connected (directly connected in one embodiment) with the second dispersive mixing zone being on the upstream side. Such an arrangement is advantageous in further improving the elongation.
[0231] It should be noted that the inflow into each zone or the outflow from each zone can be any mixture as long as it is a mixture flowing into or flowing out from each zone. For example, the outflow is not limited to the case where a discharge flow path to the outside of the extruder is pre-set in the extruder structure.
[0232] In one embodiment of the case where the second component includes organic fibers, the mass ratio of the components having a fiber diameter of 50 μm or more in the organic fibers in the inflow 41a flowing into the first dispersing and mixing zone is preferably 10% or more, or 20% or more, or 30% or more, or 40% or more, and preferably 90% or less, or 80% or less, or 70% or less, or 60% or less. That is, the inflow 41a may include a considerable amount of coarse particles.
[0233] In one embodiment, the ratio (1b / 1a) of the mass ratio (1b) of the organic fibers having a fiber diameter of 50 μm or more in the outflow 41b flowing out of the first dispersing and mixing zone to the mass ratio (1a) of the organic fibers having a fiber diameter of 50 μm or more in the inflow 41a flowing into the first dispersing and mixing zone is preferably 0 or more, or 0.1 or more, or 0.2 or more, and preferably 0.6 or less, or 0.5 or less, or 0.3 or less. In this case, the coarse particles are crushed in the first dispersing and mixing zone 41, and the coarse particles in the outflow 41b are greatly reduced.
[0234] In one embodiment, the ratio (2b / 2a) of the mass ratio (2b) of the component with a fiber diameter of 50 μm or more in the organic fibers in the outflow 42b flowing out of the second dispersion mixing zone to the mass ratio (2a) of the component with a fiber diameter of 50 μm or more in the inflow 42a flowing into the second dispersion mixing zone is preferably 0.6 or more, or 0.7 or more, or 0.8 or more, and preferably 1 or less, or 0.9 or less. In this case, microdispersion is performed in the second dispersion mixing zone 42, and on the other hand, the reduction of coarse particles from the inflow 42a to the outflow 42b is extremely small. It should be noted that in the present disclosure, when the above-mentioned mass ratios (2a) and (2b) are both 0%, the above-mentioned ratio (2b / 2a) is treated as 1.
[0235] In one embodiment, [E1] is preferably 1% or more, or 2% or more, or 3% or more, preferably 100% or less, or 50% or less, or 30% or less, [E2] is preferably 0% or more, preferably 10% or less, or 5% or less, or 3% or less, [M1] is preferably 0 GPa or more, or 0.1 GPa or more, or 0.3 GPa or more, preferably 1 GPa or less, or 0.7 GPa or less, or 0.5 GPa or less, [M2] is preferably 0.1 GPa or more, or 0.5 GPa or less. a or more, or more than 1 GPa, preferably less than 20 GPa, or less than 10 GPa, or less than 5 GPa, the absolute value of the difference between [E1] and [E2] is preferably more than 0.1%, or more than 1%, or more than 5%, preferably less than 100%, or less than 50%, or less than 30%, the absolute value of the difference between [M1] and [M2] is preferably more than 0.1 GPa, or more than 0.5 GPa, or more than 1 GPa, preferably less than 20 GPa, or less than 10 GPa, or less than 5 GPa.
[0236] In one embodiment, the zone length / barrel inner diameter ratio of each of the first and second dispersive mixing zones is preferably 1 or more, or 3 or more, or 4 or more, and is preferably 30 or less, or 20 or less, or 10 or less.
[0237] In one embodiment, the mixture filling rate of each of the first and second dispersive mixing zones is preferably 10% or more, or 50% or more, or 70% or more, and preferably 100% or less, or 99% or less, or 95% or less.
[0238] In one embodiment, the temperature of each of the first and second dispersing and mixing zones is preferably 100°C or higher, 150°C or higher, or 200°C or higher, and preferably 400°C or lower, 350°C or lower, or 300°C or lower.
[0239] In one embodiment, the pressure of the mixed material in each of the first and second dispersed mixing zones is preferably above 0 MPa, or above 0.1 MPa, or above 0.3 MPa, or above 1 MPa, and preferably below 15 MPa, or below 10 MPa, or below 5 MPa, or below 3 MPa.
[0240] In one embodiment, the space volume ratio of each of the first and second dispersive mixing zones is preferably 10% or more, or 20% or more, or 30% or more, and is preferably 70% or less, or 60% or less, or 50% or less.
[0241] The resin composition dispersed and mixed in the dispersive mixing zone 401 can be introduced into the distributive mixing zone 402 for further distributive mixing with or without passing through other zones (e.g., the melting zone 404). The mixing conditions in the distributive mixing zone are not particularly limited, and for example, distributive mixing can be performed by arbitrarily combining kneading disks such as a forward kneading disk and a neutral kneading disk.
[0242] Second Implementation Method
[0243] Figure 6 It is a figure explaining the process of the manufacturing method of the resin composition of 2nd Embodiment, Figure 7 This is a diagram for explaining the changing behaviors of tensile elongation and flexural modulus in the method of the second embodiment. The method of the second embodiment has the following features, and other than these features, the same steps and conditions as those described above with respect to the first embodiment can be appropriately adopted.
[0244] Reference Figure 6In the second embodiment, the extruder 600 has a dispersive mixing zone 601, and optionally may further have a distributive mixing zone 602, and may further have a melting zone 603 upstream of the dispersive mixing zone 601, and / or a melting zone 604 downstream of the dispersive mixing zone 601. For example, in the method of mode B, before the dispersive mixing step in the dispersive mixing zone 601, a step of melting the first component a1 in the melting zone 603 and adding the second component a2 to the obtained melt to obtain a premix may be further included, and the premix may be supplied to the dispersive mixing zone 601. After the first component a1 passes through the melting zone 603, when the second component a2 is added to the molten first component from the addition port (side feeder), thermal degradation of the second component can be suppressed, which is preferred. The mixture is dispersedly mixed and optionally distributedly mixed by the extruder 600 and taken out in the form of a resin composition b.
[0245] Reference Figure 6 and Figure 7 In the dispersion mixing zone 601, by making the treatment conditions different from each other, the travel length l of the mixture in the barrel (i.e., the flow length of the mixture in the barrel length direction L when it flows in the dispersion mixing zone 601) (mm) is divided by the barrel inner diameter d (mm) to obtain l / d, and the ratio [ΔE / ΔM] of the change in tensile elongation per unit l / d ΔE (%) to the change in bending modulus ΔM (GPa) per unit l / d is changed in the barrel length direction L. In one embodiment, the treatment conditions are one or more selected from the group consisting of the zone length / barrel inner diameter ratio, the mixture filling rate, the temperature, the pressure, and the space volume rate.
[0246] In one embodiment, the ratio [ΔE / ΔM] is gradually decreased from the upstream side of the barrel toward the downstream side. In such an embodiment, the upstream side of the barrel corresponds to the region of increased tensile elongation, and the downstream side corresponds to the region of increased bending modulus, which is advantageous from the perspective of obtaining a resin composition with higher rigidity. In this embodiment, as ΔE gradually decreases from the upstream side of the barrel toward the downstream side, ΔM may gradually increase. For example, from the entrance to the exit of the dispersed mixing zone 601, ΔE can gradually decrease from a range of more than 0.1%, or more than 1%, or more than 10%, and less than 300%, or less than 200%, or less than 100% to a range of more than 0.01%, or more than 0.1%, or more than 0.5% and less than 10%, or less than 5%, or less than 2%, and ΔM can gradually increase from a range of more than 0.001 GPa, or more than 0.01 GPa, or more than 0.05 GPa, and less than 10 GPa, or less than 5 GPa, or less than 2 GPa to a range of more than 0.02 GPa, or more than 0.05 GPa, or more than 0.1 GPa, and less than 50 GPa, or less than 10 GPa, or less than 5 GPa.
[0247] On the other hand, in another embodiment, the ratio [ΔE / ΔM] is gradually increased from the upstream side of the barrel toward the downstream side. In such an embodiment, the upstream side of the barrel corresponds to the region where the bending modulus is improved, and the downstream side corresponds to the region where the tensile elongation is improved, which is advantageous from the perspective of obtaining a resin composition with a higher elongation. In this embodiment, as ΔE gradually increases from the upstream side of the barrel toward the downstream side, ΔM may gradually decrease. For example, from the entrance to the exit of the dispersed mixing zone, ΔE can gradually increase from the range of more than 0.01%, or more than 0.1%, or more than 0.5% and less than 10%, or less than 5%, or less than 2% to the range of more than 0.1%, or more than 1%, or more than 10% and less than 300%, or less than 200%, or less than 100%, and ΔM can gradually decrease from the range of more than 0.02 GPa, or more than 0.05 GPa, or more than 0.1 GPa and less than 50 GPa, or less than 10 GPa, or less than 5 GPa to the range of more than 0.001 GPa, or more than 0.01 GPa, or more than 0.05 GPa and less than 10 GPa, or less than 5 GPa, or less than 2 GPa.
[0248] Method C
[0249] The method of mode C of the present disclosure includes a dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and a distributing mixing step of distributing and mixing at least the dispersive mixing product in a distributing mixing zone of an extruder to obtain a resin composition. The method of mode C has the following characteristics, and in addition to this characteristic, one or more of the above-mentioned characteristics exemplified in mode A can be combined. In one embodiment, the dispersive mixing zone of mode C can have a high load zone (more specifically, a narrow gap zone, a pressure reduction zone, or a high pressure zone) of mode A.
[0250] [1] A method for producing a resin composition comprising a first component and a second component, wherein:
[0251] The above method comprises the following steps:
[0252] A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and
[0253] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0254] The dispersive mixing zone and the distributive mixing zone are different from each other in one or more selected from the group consisting of zone length / barrel inner diameter ratio, mixture filling rate, temperature, pressure and space volume rate,
[0255] The increment [EA] of the tensile elongation of the outflow from the above-mentioned dispersive mixing zone relative to the tensile elongation of the inflow into the above-mentioned dispersive mixing zone and the increment [EB] of the tensile elongation of the outflow from the above-mentioned distribution mixing zone relative to the tensile elongation of the inflow into the above-mentioned distribution mixing zone satisfy the relationship [EA]>[EB],
[0256] The increment [MA] of the bending modulus of the outflow from the above-mentioned dispersed mixing zone relative to the bending modulus of the inflow into the above-mentioned dispersed mixing zone and the increment [MB] of the bending modulus of the outflow from the above-mentioned distributed mixing zone relative to the bending modulus of the inflow into the above-mentioned distributed mixing zone satisfy the relationship [MA]>[MB].
[0257] [2] A method as described in method 1 above, wherein the above [EA] is 1% to 100%, the above [EB] is 0% to 10%, the above [MA] is 0.1 GPa to 20 GPa, the above [MB] is 0 GPa to 1 GPa, the difference between [EA] and [EB] ([EA]-[EB]) is 0.01% to 100%, and the difference between [MA] and [MB] ([MA]-[MB]) is 0.001 GPa to 10 GPa.
[0258] [3] A method as described in method 1 or 2 above, wherein in the area where the ratio of the zone length to the inner diameter of the barrel in the dispersed mixing zone is greater than 1, and in the area where the ratio of the zone length to the inner diameter of the barrel in the distributed mixing zone is less than 5, the pressure of the mixed mixture is greater than 0.3 MPa.
[0259] [4] A method for producing a resin composition comprising a first component and a second component, wherein:
[0260] The above method comprises the following steps:
[0261] A dispersive mixing step of dispersing and mixing the cellulose fibers and the resin in a dispersive mixing zone of the extruder to obtain a dispersive mixing product; and
[0262] A distributing and mixing step of distributing and mixing at least the above-mentioned dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition,
[0263] The concentration [CA] of the second component in the dispersive mixing zone is 10% to 90% by mass, the concentration [CB] of the second component in the distributive mixing zone is 1% to 50% by mass, and the ratio [CA] / [CB] is 2 to 90.
[0264] [5] A method as described in any one of the above-mentioned methods 1 to 4, wherein the increment [TA] of the thixotropic index of the effluent flowing out of the above-mentioned dispersed mixing zone relative to the thixotropic index of the influent flowing into the above-mentioned dispersed mixing zone and the increment [TB] of the thixotropic index of the effluent flowing out of the above-mentioned distributed mixing zone relative to the thixotropic index of the influent flowing into the above-mentioned distributed mixing zone satisfy the relationship [TA]>[TB].
[0265] [6] A method as described in the above-mentioned embodiment 5, wherein the above-mentioned [TA] is greater than 0.01 and less than 10, the above-mentioned [TB] is greater than 0.01 and less than 10, and the above-mentioned [TA] / [TB] ratio is greater than 1 and less than 100.
[0266] [7] The method according to any one of aspects 1 to 6 above, wherein the rate of improvement of the physical property per unit mass of the second component in the mixture is greater in the distributive mixing zone than in the dispersive mixing zone.
[0267] [8] A method as described in any one of the above methods 1 to 7, further comprising a step of adding an additional polymer to the above-mentioned dispersed mixing product after the above-mentioned dispersed mixing step and before the above-mentioned distributed mixing step to obtain an additional polymer mixture, and supplying the above-mentioned additional polymer mixture to the above-mentioned distributed mixing zone.
[0268] [9] A method as described in any one of the above methods 1 to 8, wherein the second component comprises organic fibers, preferably cellulose fibers, and the organic fibers in the resin composition have an average fiber diameter of less than 1000 nm and an average fiber length / average fiber diameter ratio of more than 30.
[0269] In the method of form C, the tensile elongation and flexural modulus are not increased by dispersive mixing and distributive mixing, but a certain degree of large force is applied to the second component during dispersive mixing, so that the tensile elongation and flexural modulus of the mixture are significantly improved. On the other hand, during distributive mixing, the mixing conditions are relaxed in such a way that the force applied to the second component is minimized, and the increase in tensile elongation and flexural modulus is small, but damage to the second component can be avoided. In the molded body formed by the resin composition obtained through such a treatment step, the tensile elongation and flexural modulus can be unexpectedly high and stable.
[0270] Figure 8 This is a diagram for explaining the steps of a method for producing a resin composition according to one embodiment of the present invention. Figure 8 , the extruder 800 has a dispersive mixing zone 801 and a distributive mixing zone 802. In a representative manner, as Figure 8As shown, a distributive mixing zone 802 is disposed downstream of the dispersive mixing zone 801. The extruder 800 may further include a melting zone 803 upstream of the dispersive mixing zone 801 and / or a melting zone 804 downstream of the dispersive mixing zone 801 and upstream of the distributive mixing zone 802.
[0271] The method of mode C may further include a step of melting the first component a1 in the melting zone 803 and adding the second component a2 to the obtained melt to obtain a premix before the dispersive mixing step in the dispersive mixing zone 801, and the premix may be supplied to the dispersive mixing zone 801. In conventional kneading using an extruder, a strong shear is applied to the mixture in the initial melting zone, so after the first component passes through the melting zone, when the second component is added to the molten first component from the addition port (side feeder), thermal degradation of the second component can be suppressed. The mixture is dispersed and distributed by the extruder 800 and taken out in the form of a resin composition b.
[0272] In addition, the method of mode C may further include a step of adding an additional polymer of the same or different type, preferably the same type, as the first component in the dispersed mixing product to the dispersed mixing product after the dispersed mixing step and before the distributed mixing step to obtain an additional polymer mixture, and the additional polymer mixture may be supplied to the distributed mixing zone. For example, the additional polymer may be added to the effluent flowing out of the dispersed mixing zone 801 (for example, by Figure 8 After the additional polymer is fed to the melting zone 804 (side feeding of the additional polymer), it is supplied to the distribution mixing zone 802. The amount of the additional polymer added can be determined according to the kneading conditions, the desired concentration of the second component of the resin composition, etc., for example, it can be 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 50 parts by mass or more relative to 100 parts by mass of the dispersed mixed product, and can be 1000 parts by mass or less, or 500 parts by mass or less, or 400 parts by mass or less, or 300 parts by mass or less. In one embodiment, the concentration of the second component of the dispersed mixed product can be made to be greater than 10 mass%, or greater than 20 mass%, or greater than 25 mass%, or greater than 30 mass%, and / or less than 80 mass%, or less than 70 mass%, or less than 60 mass%, or less than 50 mass%, and the concentration of the second component of the additional polymer mixture (which in one embodiment is equal to the concentration of the second component in the resin composition) can be made to be greater than 1 mass%, or greater than 2 mass%, or greater than 3 mass%, or greater than 5 mass%, and / or less than 50 mass%, or less than 40 mass%, or less than 30 mass%, or less than 20 mass%.
[0273] (Based on cooling with additional polymer)
[0274] The additional polymer may have a lower temperature than the dispersed mixed product, thereby cooling the dispersed mixed product. The temperature of the additional polymer added for cooling is, in one embodiment, 0°C or more, or 10°C or more, or 20°C or more, in one embodiment, 300°C or less, or 200°C or less, or 100°C or less, or 50°C or less. The temperature of the dispersed mixed product to which the additional polymer is added is, in one embodiment, 100°C or more, or 150°C or more, or 200°C or more, in one embodiment, 450°C or less, or 400°C or less, or 350°C or less.
[0275] Mode C more specifically includes the following first and second embodiments.
[0276] 《First embodiment (processing condition control)》
[0277] Refer again Figure 8 In the first embodiment, the processing conditions of the dispersive mixing zone 801 and the distributive mixing zone 802 are different from each other. In one embodiment, the processing conditions are one or more selected from the group consisting of the zone length / barrel inner diameter ratio, the mixture filling rate, the temperature, the pressure and the space volume rate.
[0278] The zone lengths noted above are the combined lengths of the screw elements that make up the dispersive mixing zone and the distributive mixing zone and depend on the screw configuration.
[0279] The mixture filling rate is the ratio of the actual filling amount (volume basis) of the mixture to the spatial volume of the extruder. After the rotation of the screw and the supply of raw materials are suddenly stopped, the screw is pulled out, and the mixture attached to the screw surface is collected and measured, and the volume filled with the mixture is calculated by dividing it by the density of the mixture. Then, the volume filled with the mixture is divided by the spatial volume described later to calculate the mixture filling rate. The mixture filling rate depends on the screw structure and extrusion conditions.
[0280] The above-mentioned space volume ratio is calculated by subtracting the screw volume (the sum of the element volume and the shaft volume) from the barrel volume of the extruder to calculate the space volume, and dividing the space volume by the barrel volume. The space volume ratio depends on the screw structure.
[0281] In one embodiment, the increment [EA] of the tensile elongation of the effluent flowing out of the dispersed mixing zone 801 relative to the tensile elongation of the influent flowing into the dispersed mixing zone 801 and the increment [EB] of the tensile elongation of the effluent flowing out of the distributed mixing zone 802 relative to the tensile elongation of the influent flowing into the distributed mixing zone 802 satisfy the relationship [EA]>[EB], and the increment [MA] of the bending modulus of the effluent flowing out of the dispersed mixing zone 801 relative to the bending modulus of the influent flowing into the dispersed mixing zone 801 and the increment [MB] of the bending modulus of the effluent flowing out of the distributed mixing zone 802 relative to the bending modulus of the influent flowing into the distributed mixing zone 802 satisfy the relationship [MA]>[MB].
[0282] It should be noted that the inflow into each zone or the outflow from each zone can be a mixture flowing into each zone or flowing out from each zone. For example, the outflow is not limited to the case where a discharge flow path to the outside of the extruder is pre-set in the extruder structure.
[0283] [EA] is preferably 1% or more, 2% or more, or 3% or more, and preferably 100% or less, 50% or less, or 30% or less. [EB] is preferably 0% or more, 0.1% or more, or 0.5% or more, and preferably 10% or less, 5% or less, or 3% or less.
[0284] [MA] is preferably 0.1 GPa or more, or 0.5 GPa or more, or 1 GPa or more, and preferably 20 GPa or less, or 10 GPa or less, or 5 GPa or less. [MB] is preferably 0 GPa or more, or 0.1 GPa or more, or 0.3 GPa or more, and preferably 1 GPa or less, or 0.7 GPa or less, or 0.5 GPa or less.
[0285] The difference between [EA] and [EB] ([EA] - [EB]) is preferably 0.01% or more, 0.1% or more, or 1% or more, and is preferably 100% or less, 50% or less, or 10% or less.
[0286] The difference between [MA] and [MB] ([MA] - [MB]) is preferably 0.001 GPa or more, 0.01 GPa or more, or 0.1 GPa or more, and is preferably 10 GPa or less, 5 GPa or less, or 1 GPa or less.
[0287] In one embodiment, the zone length / barrel inner diameter ratio of each zone of the dispersive mixing zone 801 and the distributive mixing zone 802 is preferably greater than 1, or greater than 3, or greater than 4, and preferably less than 30, or less than 20, or less than 10.
[0288] In one embodiment, the mixture filling rate of each zone of the dispersed mixing zone 801 and the distributed mixing zone 802 is preferably 10% or more, 50% or more, or 70% or more, and preferably 100% or less, 99% or less, or 95% or less.
[0289] In one embodiment, the temperature of each zone of the dispersive mixing zone 801 and the distributive mixing zone 802 is preferably above 100°C, or above 150°C, or above 200°C, and preferably below 400°C, or below 350°C, or below 300°C.
[0290] In one embodiment, the pressure of the mixed material in each zone of the dispersed mixing zone 801 and the distributed mixing zone 802 is preferably above 0 MPa, or above 0.1 MPa, or above 0.3 MPa, or above 1 MPa, and preferably below 15 MPa, or below 10 MPa, or below 5 MPa, or below 3 MPa.
[0291] In one embodiment, the spatial volume ratio of each zone of the dispersed mixing zone 801 and the distributed mixing zone 802 is preferably 10% or more, or 20% or more, or 30% or more, and preferably 70% or less, or 60% or less, or 50% or less.
[0292] In one embodiment, in the area where the zone length / barrel inner diameter ratio of the dispersed mixing zone 801 is 1 or more, or 2 or more, or 5 or more, and the zone length / barrel inner diameter ratio of the distributed mixing zone 802 is 5 or less, or 2 or less, or 1 or less, the pressure of the mixed material is 0.1 MPa or more, or 0.2 MPa or more, or 0.3 MPa or more, or 0.5 MPa or more, or 1 MPa or more, or 3 MPa or more, or 5 MPa or more, or 7 MPa or more. From the perspective of suppressing damage to the second component, the pressure of the mixed material can preferably be 20 MPa or less, or 15 MPa or less, or 10 MPa or less. In this case, the area where high pressure is applied to the mixed material can be made wider in the dispersed mixing zone 801 and narrower in the distributed mixing zone 802. As a result, the second component can be finely refined in the dispersed mixing zone 801, and on the other hand, the dispersion state of the second component in the first component can be improved in the distributed mixing zone 802 while avoiding damage to the second component. The region where the pressure of the mixed material is within the above range may be a region where the ratio of the zone length to the barrel inner diameter of the dispersive mixing zone 801 is 30 or less, or 20 or less, or 10 or less.
[0293] In one embodiment, in the region where the zone length / barrel inner diameter ratio of the dispersive mixing zone is 1 or more and the zone length / barrel inner diameter ratio of the distributive mixing zone is 5 or less, the pressure of the mixed material is 0.3 MPa or more.
[0294] In one embodiment, from the perspective of improving the dispersion of the second component and forming more practical characteristics, the rate of improvement of the physical property per unit mass of the second component in the mixture is greater in the distribution mixing zone than in the dispersion mixing zone. The rate of improvement of the physical property in the dispersion mixing zone is the ratio of the physical property of the effluent flowing out of the dispersion mixing zone to the physical property of the influent flowing into the dispersion mixing zone, and the rate of improvement of the physical property in the distribution mixing zone is the ratio of the physical property of the effluent flowing out of the distribution mixing zone to the physical property of the influent flowing into the distribution mixing zone. In one embodiment, the physical property is selected from tensile elongation and flexural modulus. Regarding the ratio of the distribution mixing zone to the dispersion mixing zone of the above-mentioned physical property improvement rate, from the above-mentioned aspects, it is preferably greater than 1, or is greater than 1.2, or is greater than 1.5, and from the aspect of the ease of designing the processing conditions, it can be, for example, less than 100, or less than 10, or less than 5.
[0295] <<Second embodiment (control of concentration of second component)>>
[0296] Refer again Figure 8 In the second embodiment, the concentration [CA] of the second component in the dispersive mixing zone 801 is 10% to 90% by mass, the concentration [CB] of the second component in the distributive mixing zone 802 is 1% to 50% by mass, and the ratio [CA] / [CB] is 2 to 90. For example, the effluent from the dispersive mixing zone 801 may be supplemented with an additional polymer (e.g., by Figure 8 The concentration of the second component is adjusted to the above range by a method of adding a side feed of a polymer to the melting zone 804 of the dispersive mixing zone 801 and then supplying the second component to the distributive mixing zone 802. By adjusting the concentrations of the second components in the dispersive mixing zone 801 and the distributive mixing zone 802 as described above, it is possible to simultaneously achieve miniaturization of the second component in the dispersive mixing zone 801 and improve the dispersion state of the second component while avoiding damage to the second component in the distributive mixing zone 802.
[0297] Regarding the above-mentioned concentration [CA], from the perspective of good miniaturization of the second component, in one embodiment, it is 10 mass % or more, or 15 mass % or more, or 20 mass % or more, and from the perspective of suppressing damage to the second component, in one embodiment, it is 90 mass % or less, or 80 mass % or less, or 70 mass % or less.
[0298] Regarding the above-mentioned concentration [CB], from the perspective of adjusting the concentration of the second component in the resin composition according to various uses, in one embodiment, it is 1 mass % or more, or 5 mass % or more, or 10 mass % or more, and from the perspective of suppressing damage to the second component, in one embodiment, it is 50 mass % or less, or 40 mass % or less, or 30 mass % or less.
[0299] The above ratio [CA] / [CB] is 2 or more, 3 or more, or 4 or more in one embodiment from the perspective of promoting the refinement of the second component in the dispersion mixing step and suppressing damage in the distribution mixing step. In one embodiment, it is 90 or less, 50 or less, or 10 or less from the perspective of avoiding damage to the second component due to an excessively high concentration [CA] or limiting the application of the resin composition due to an excessively low concentration [CB].
[0300] 《Changes in Thixotropic Index》
[0301] In one embodiment, the increment [TA] of the thixotropic index of the outflow from the dispersive mixing zone 801 relative to the thixotropic index of the inflow into the dispersive mixing zone 801 and the increment [TB] of the thixotropic index of the outflow from the distributive mixing zone 802 relative to the thixotropic index of the inflow into the distributive mixing zone 802 satisfy the relationship [TA]>[TB]. The larger the increment [TA], the more the second component is refined in the dispersive mixing zone 801, and the larger the increment [TB], the more the second component is refined in the distributive mixing zone 802. [TA]>[TB] is an indicator that the dispersive mixing zone 801 has a higher priority in refining the second component than the distributive mixing zone 802.
[0302] The [TA] / [TB] ratio is preferably greater than 1, or 2 or more, or 3 or more, from the perspective of preferentially refining the second component in the dispersive mixing zone 801, and is preferably 100 or less, or 50 or less, or 10 or less, from the perspective of suppressing damage to the second component due to excessive refining of the second component in the dispersive mixing zone 801. The method for measuring the thixotropic index is as follows.
[0303] The increment [TA] is preferably greater than 0.01 and not more than 10, or 0.05 to 5, or 0.1 to 2.
[0304] The increment [TB] is preferably 0.01 or more and less than 10, or 0.05 to 5, or 0.1 to 2.
[0305] [Extrusion of resin composition]
[0306] In the methods of methods A to C, the resin composition b leaving the kneading zone 101, 201, 301 (for method A), the distribution mixing zone 402, 602 (for method B), or the distribution mixing zone 802 (for method C) can be extruded out of the extruder in a desired shape. For example, from the perspective of ease of post-processing and transportation, the pellet form is preferred. Preferred examples of pellet forms include round, elliptical, cylindrical, etc., which vary depending on the cutting method during extrusion processing. As the size of the round pellet, the diameter of 1 mm to 3 mm can be exemplified, and as the size of the cylindrical pellet, the diameter of 1 mm to 3 mm and the length of 2 mm to 10 mm can be exemplified. Regarding the above-mentioned diameter and length, it is preferably above the lower limit from the perspective of operational stability during extrusion, and it is preferably below the upper limit from the perspective of the bite into the molding machine in post-processing.
[0307] [Manufacturing of Molded Article]
[0308] The resin composition produced by the methods A to C can be formed into various forms of molded bodies such as films, sheets, fibers, plates, powders, and three-dimensional structures. Examples of molding methods include injection molding, extrusion molding, foam molding, insert molding, in-mold coating molding, and mold molding. For example, various extrusion moldings are suitable for molding sheets, films, fibers, and the like. The molding temperature can be appropriately selected according to the composition of the resin composition, for example, it can be above the melting point of the resin used, or above the melting point + 20°C, or above the melting point + 30°C, and can be below the melting point + 90°C, or below the melting point + 80°C, or below the melting point + 70°C.
[0309] [Material components of resin composition]
[0310] The resin composition disclosed herein, in particular, produced by the methods of methods A to C, contains a first component as a polymer, and a second component as an organic fiber and / or a polymer different from the first component. Regarding the polymer different from the first component, in one embodiment, it refers to a polymer having a molecular structure and / or a molecular weight different from the first component. The polymer in the first component, the organic fiber in the second component, and the polymer in the second component can be one type or two or more types, respectively. In one embodiment, regarding the polymer in the first component and the polymer in the second component, the molecular structure and / or molecular weight of at least one polymer constituting them are different from each other. Regarding the second component, in one embodiment, it is an organic fiber, in one embodiment, it is a polymer, and in one embodiment, it is a combination of an organic fiber and a polymer. As material components used to manufacture the resin composition and thus contained in the resin composition, the following components can be exemplified.
[0311] "Ingredient 1"
[0312] The first component is a polymer in one embodiment. The polymer can be appropriately selected according to the purpose of use of the resin composition, for example, it can be a crystalline thermoplastic resin having a melting point in the range of 100°C to 350°C, an amorphous thermoplastic resin having a glass transition point in the range of 100 to 250°C, etc. As the polymer, polyolefin resins, polyamide resins, polyester resins, polyacetal resins, polyphenylene ether resins, polyphenylene sulfide resins and mixtures of two or more thereof can be exemplified. From the perspective of handling and cost, polyolefin resins, polyamide resins, polyester resins, polyacetal resins, etc. can be preferably cited, more preferably polyamide resins, polyolefin resins and polyacetal resins, and particularly preferably polyamide resins and polyacetal resins. From the perspective of improving the heat resistance of the resin composition, the melting point of the thermoplastic resin (especially crystalline resin) is preferably 140°C or more, or 150°C or more, or 160°C or more, or 170°C or more, or 180°C or more, or 190°C or more, or 200°C or more, or 210°C or more, or 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more.
[0313] The melting point of the thermoplastic resin may be, for example, 150°C to 190°C or 160°C to 180°C for a resin having a relatively low melting point (e.g., a polyolefin resin), and may be, for example, 220°C to 350°C or 230°C to 320°C for a resin having a relatively high melting point (e.g., a polyamide resin).
[0314] In the present disclosure, the melting point refers to the peak top temperature of the endothermic peak that appears when the temperature is raised from 23°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC), and when two or more endothermic peaks appear, it refers to the peak top temperature of the endothermic peak on the highest temperature side. In addition, in the present disclosure, the glass transition point refers to the temperature obtained using a dynamic viscoelasticity measuring device as described above.
[0315] Preferred polyolefin resins as polymers are olefins (e.g., α-olefins) or polymers obtained by polymerizing olefins as monomer units. Specific examples of polyolefin resins include: ethylene (co)polymers exemplified by low-density polyethylene (e.g., linear low-density polyethylene), high-density polyethylene, ultra-low-density polyethylene, ultra-high molecular weight polyethylene, etc.; polypropylene (co)polymers exemplified by polypropylene, ethylene-propylene copolymers, ethylene-propylene-diene copolymers, etc.; α-olefin copolymers of ethylene such as ethylene-acrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-glycidyl methacrylate copolymers, etc., etc.
[0316] Here, as the most preferred polyolefin resin, polypropylene can be cited. Polypropylene having a melt flow rate (MFR) of 3 g / 10 min or more and 30 g / 10 min or less measured at 230 ° C and a load of 21.2 N according to ISO1133 is particularly preferred. The lower limit of MFR is more preferably 5 g / 10 min, further more preferably 6 g / 10 min, and most preferably 8 g / 10 min. In addition, the upper limit is more preferably 25 g / 10 min, further more preferably 20 g / 10 min, and most preferably 18 g / 10 min. Regarding MFR, it is preferably not higher than the above upper limit from the aspect of improving the toughness of the composition, and is preferably not lower than the above lower limit from the aspect of the fluidity of the composition.
[0317] In addition, in order to improve the affinity with cellulose, acid-modified polyolefin resins can also be appropriately used. As the acid at this time, it can be appropriately selected from polycarboxylic acids such as maleic acid, fumaric acid, succinic acid, phthalic acid and their anhydrides, and citric acid. Among these, maleic acid or its anhydride is preferred from the aspect of improving the ease of modification rate. There is no particular restriction on the modification method, which is usually a method of heating to a melting point or above in the presence or absence of peroxide for melt mixing. As an acid-modified polyolefin resin, all of the above-mentioned polyolefin resins can be used, and polypropylene can be preferably used. Acid-modified polypropylene can be used alone, but in order to adjust the modification rate of the entire resin, it is more preferably mixed with unmodified polypropylene. At this time, the ratio of acid-modified polypropylene to total polypropylene is 0.5% to 50% by mass. The more preferred lower limit is 1% by mass, more preferably 2% by mass, further more preferably 3% by mass, particularly preferably 4% by mass, and most preferably 5% by mass. In addition, the upper limit is more preferably 45% by mass, further preferably 40% by mass, further more preferably 35% by mass, particularly preferably 30% by mass, and most preferably 20% by mass. In order to maintain the interface strength between the first component and the second component (in one embodiment, the interface strength between the resin and the cellulose), it is preferably above the lower limit, and in order to maintain the ductility as a resin, it is preferably below the upper limit.
[0318] The melt flow rate (MFR) of the acid-modified polypropylene measured at 230°C and a load of 21.2N according to ISO1133 is preferably 50 g / 10 minutes or more in order to improve the affinity with the interface between the first component and the second component (for example, the interface between cellulose and the resin). The more preferred lower limit is 100 g / 10 minutes, further preferably 150 g / 10 minutes, and most preferably 200 g / 10 minutes. The upper limit is not limited, but is 500 g / 10 minutes from the perspective of maintaining mechanical strength. By making the MFR within this range, the advantage of being easily present at the interface between the first component and the second component (in one embodiment, the interface between cellulose and the resin) can be enjoyed.
[0319] Examples of the polyamide resin include polyamide 6, polyamide 11, and polyamide 12 obtained by polycondensation of lactams; and diamines such as 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,7-heptanediamine, 2-methyl-1-6-hexanediamine, 1,8-octanediamine, 2-methyl-1,7-heptanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecaneamine, and meta-xylylenediamine with succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. Polyamide 6,6, polyamide 6,10, polyamide 6,11, polyamide 6,12, polyamide 6,T, polyamide 6,I, polyamide 9,T, polyamide 10,T, polyamide 2M5,T, polyamide MXD,6, polyamide 6,C, polyamide 2M5,C and copolymers thereof obtained by copolymerizing dicarboxylic acids such as benzene-1,2-dicarboxylic acid, benzene-1,3-dicarboxylic acid, benzene-1,4-dicarboxylic acid, cyclohexane-1,3-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, etc., and copolymers such as polyamide 6,T / 6,I are mentioned as an example.
[0320] Among these polyamide-based resins, more preferred are aliphatic polyamides such as polyamide 6, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,11, and polyamide 6,12; and alicyclic polyamides such as polyamide 6,C and polyamide 2M5,C.
[0321] The terminal carboxyl group concentration of the polyamide resin is not particularly limited, but may be preferably 20 μmol / g or more, or 25 μmol / g or more, and may be preferably 150 μmol / g or less, or 100 μmol / g or less.
[0322] The terminal amino group concentration of the polyamide resin may preferably be 20 μmol / g or more, or 30 μmol / g or more, and may preferably be 150 μmol / g or less, or 100 μmol / g or less.
[0323] The total concentration of the terminal amino group and the terminal carboxyl group of the polyamide resin is not particularly limited, and may preferably be 10 μmol / g or more, or 50 μmol / g or more, or 100 μmol / g or more, or 135 μmol / g or more. From the perspective of preventing a decrease in viscosity due to an excessively low molecular weight of the resin and inhibiting the generation of burrs during molding, the total concentration may preferably be 500 μmol / g or less, or 300 μmol / g or less, or 135 μmol / g or less, or 100 μmol / g or less.
[0324] The ratio of the amino terminal group to the carboxyl terminal group of the polyamide resin ([NH2] / [COOH]) is preferably greater than 1.00, or 1.01 or more, or 1.05 or more, or 1.10 or more. The upper limit of the amino terminal group ratio is not particularly limited, but from the perspective of maintaining the color tone of the resin composition well, it can be preferably 10000 or less, or 100 or less, or 10 or less.
[0325] As a method for adjusting the terminal group concentration of the polyamide resin, a known method can be used. For example, a method can be mentioned in which a terminal adjusting agent that reacts with the terminal group, such as a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacyl halide, a monoester, a monoalcohol, etc., is added to the polymerization liquid so as to achieve a predetermined terminal group concentration during the polymerization of the polyamide.
[0326] The concentration of amino terminal groups and carboxyl terminal groups of polyamide resins can be determined by 1 H-NMR is obtained from the integrated value of the characteristic signal corresponding to each terminal group. Specifically, the method described in Japanese Patent Application Laid-Open No. 7-228775 is recommended.
[0327] The intrinsic viscosity [η] of the polyamide resin measured in concentrated sulfuric acid at 30°C is preferably 0.6 to 2.0 dL / g, more preferably 0.7 to 1.4 dL / g, further preferably 0.7 to 1.2 dL / g, and particularly preferably 0.7 to 1.0 dL / g. When a polyamide having an intrinsic viscosity within the above range is used, the advantages of improving the in-mold fluidity of the resin composition during injection molding and improving the appearance of the molded sheet can be obtained.
[0328] In the present disclosure, “intrinsic viscosity” has the same meaning as viscosity generally referred to as limiting viscosity, and can be measured by the method described in, for example, Polymer Process Engineering (Prentice-Hall, Inc. 1994), pages 291 to 294.
[0329] As the polyester resin, one or more of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene succinate (PBS), polybutylene succinate / adipate (PBSA), polybutylene terephthalate-adipate (PBAT), polyhydroxyalkanoic acid (PHA), polylactic acid (PLA), polyarylate (PAR), polycarbonate (PC), etc. can be used. As the polyester resin, PET, PBS, PBSA, PBT, and PEN can be more preferably mentioned, and PBS, PBSA, and PBT can be further preferably mentioned.
[0330] In addition, the polyester resin can freely change the terminal group according to the monomer ratio during polymerization, whether a terminal stabilizer is added, and the amount of the terminal stabilizer added. The ratio of the carboxyl terminal group of the polyester resin to the total terminal groups ([COOH] / [total terminal groups]) is more preferably 0.30 to 0.95. The lower limit of the carboxyl terminal group ratio is more preferably 0.35, further more preferably 0.40, and most preferably 0.45. In addition, the upper limit of the carboxyl terminal group ratio is more preferably 0.90, further more preferably 0.85, and most preferably 0.80. Regarding the above-mentioned carboxyl terminal group ratio, it is preferably 0.30 or more from the perspective of the dispersibility of cellulose in the composition, and is preferably 0.95 or less from the perspective of the color tone of the resulting composition.
[0331] As polyacetal resin, it is usually a homoacetal with formaldehyde as a raw material, and a coacetal containing trioxymethylene as a main monomer and 1,3-dioxolane as a comonomer component. Both can be used, and coacetal can be preferably used from the aspect of thermal stability during processing. In particular, the amount of the structure derived from the comonomer component (such as 1,3-dioxolane) is more preferably in the range of 0.01 to 4 mol%. The preferred lower limit of the amount of the structure derived from the comonomer component is 0.05 mol%, more preferably 0.1 mol%, and further more preferably 0.2 mol%. In addition, the preferred upper limit is 3.5 mol%, more preferably 3.0 mol%, further more preferably 2.5 mol%, and most preferably 2.3 mol%.
[0332] From the viewpoint of thermal stability during extrusion processing and molding processing, the lower limit is preferably within the above range, and from the viewpoint of mechanical strength, the upper limit is preferably within the above range.
[0333] As the polymer, for example, from the aspect of affinity with cellulose, a polymer having a hydrophilic group (for example, one or more selected from hydroxyl, amino and carboxyl groups) is particularly preferred. Preferred examples of the polymer having a hydrophilic group are one or more selected from the group consisting of acid-modified polyolefin resins, polyacetal resins, polycarbonate resins, polyamide resins, polyester resins, polyphenylene ether resins and acrylic resins. Among them, polyamide resins and maleated polypropylene are preferred.
[0334] "Second Ingredient"
[0335] The second component is organic fiber and / or polymer. In one mode, the second component is dispersed in the first component by mixing with the first component, and compared with the situation that the second component is not present, the physical property of the resin combination can be improved (in one mode, for being selected from the group consisting of tensile elongation, flexural modulus, thermal expansion coefficient and physical property stability, more than 1, preferably all of these physical properties). In the resin combination, the amount of the second component relative to the total 100 mass % of the resin combination or the amount of the second component relative to the total 100 mass % of the first component and the second component is preferably respectively more than 0.1 mass %, or more than 0.5 mass %, or more than 1 mass %, or more than 3 mass %, preferably less than 30 mass %, or less than 25 mass %, or less than 20 mass %, or less than 15 mass %. When the amount of the second component is the above-mentioned range, it is preferred from the aspect of high tensile elongation, high flexural modulus, low thermal expansion coefficient and / or good physical property stability.
[0336] Preferred examples of each of the organic fiber and the polymer are described below.
[0337] <Organic Fiber>
[0338] Organic fiber is a fiber made of organic material. In one embodiment, the organic fiber is a polymer fiber, in one embodiment, it is a fiber having a hydrogen bond forming structure (e.g., OH structure and / or NH structure), and in one embodiment, it is one or more selected from the group consisting of natural fibers (e.g., cellulose fibers, cellulose nanocrystals, chitin fibers, chitosan fibers, wool, etc.) and synthetic fibers (e.g., aramid fibers, nylon fibers, acrylic fibers, polyester fibers, vinylon fibers, rayon fibers, polyurethane fibers, etc.). In the present disclosure, cellulose fiber refers to cellulose with an L / D of 30 or more, and cellulose nanocrystals refer to cellulose with an average fiber diameter of 1000 nm or less and an L / D of less than 30. Organic fibers having a hydrogen bond forming structure have a tendency to be substantially condensed due to hydrogen bonds, and according to the method of the present disclosure, even such organic fibers can be well microdispersed in the first component.
[0339] In the resin composition, the amount of organic fibers relative to 100% by mass of the entire resin composition is preferably 0.1% by mass or more, or 0.5% by mass or more, or 1% by mass or more, or 3% by mass or more, and preferably 30% by mass or less, or 25% by mass or less, or 20% by mass or less, or 15% by mass or less. The amount of organic fibers in the above range is preferred from the perspective of high tensile elongation, high flexural modulus, low thermal expansion coefficient and / or good physical property stability.
[0340] [Cellulose fiber]
[0341] In one embodiment, the organic fiber includes cellulose fiber or is cellulose fiber. As the raw material of cellulose fiber, natural cellulose fiber and regenerated cellulose fiber can be cited. As natural cellulose fiber, wood pulp obtained from wood (broadleaf tree or coniferous tree), non-wood pulp obtained from non-wood (bamboo, hemp fiber, bagasse, kenaf, cotton lint, etc.), and their refined pulp (refined cotton lint, etc.) can be used. As non-wood pulp, cotton-derived pulp including cotton lint pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, straw-derived pulp, etc. can be used. Cotton-derived pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, and straw-derived pulp include cellulose fibers made from refined pulp obtained from raw materials such as lint, cotton linters, hemp-based abaca (e.g., abaca from Ecuador or the Philippines), sisal, bagasse, kenaf, bamboo, and straw, through a refining step such as delignification by steaming treatment, a bleaching step, and the like.
[0342] In one embodiment, the cellulose fibers are cellulose nanofibers. Cellulose nanofibers can be obtained, for example, by treating the pulp with hot water at 100° C. or higher to partially hydrolyze the hemicellulose to make it brittle, and then opening the fibers using a high-pressure homogenizer, microfluidizer, ball mill, disc mill, or other pulverizing method.
[0343] Regarding the number average fiber diameter of cellulose nanofibers, in one embodiment, it is 2 to 1000 nm, preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, or 50 nm or more, or 100 nm or more, and preferably 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less, or 200 nm or less.
[0344] The number average fiber length / number average fiber diameter ratio (L / D) of the cellulose nanofibers may be 30 or more, 50 or more, 80 or more, or 100 or more in one embodiment, and may be 5000 or less, 4000 or less, or 3000 or less in one embodiment.
[0345] In one embodiment, the number average fiber diameter (D), number average fiber length (L) and L / D ratio of the cellulose fibers disclosed in the present invention are values measured using a scanning electron microscope (SEM) according to the following steps. The aqueous dispersion of cellulose fibers is replaced with tert-butyl alcohol, diluted to 0.001-0.1% by mass, and dispersed using a high shear homogenizer (e.g., manufactured by IKA, trade name "ULTRA-TURRAX T18") at a rotation speed of 15,000 rpm × 3 minutes. The dispersion is poured on a silicon substrate on which osmium vapor is deposited, air-dried, and used as a measurement sample, and measured using a high-resolution scanning electron microscope (SEM) to obtain the result. Specifically, in an observation field adjusted for magnification in a manner such that at least 100 fibrous substances are observed, the length (L) and fiber diameter (D) of 100 randomly selected fibrous substances are measured, and the ratio (L / D) is calculated. For cellulose fibers, the number average of the length (L), the number average of the fiber diameter (D), and the number average of the ratio (L / D) are calculated.
[0346] It should be noted that the length, fiber diameter and L / D ratio of the cellulose fibers in the resin composition and the molded body can be determined by dissolving the polymer component in an organic or inorganic solvent that can dissolve the polymer component, separating the cellulose fibers, and washing them thoroughly with the above-mentioned solvent, replacing them with tert-butanol, preparing a 0.001 to 0.1 mass % dispersion, and redispersing them using a high shear homogenizer (e.g., manufactured by IKA, trade name "ULTRA-TURRAX T18"), and using the redispersed material for measurement using the above-mentioned method.
[0347] The crystallinity of the cellulose fiber is preferably 55% or more, or 60% or more, or 70% or more, or 80% or more, from the perspective of obtaining a resin composition having excellent heat resistance, mechanical strength and dimensional stability. When the crystallinity is within this range, the mechanical properties (heat resistance, strength, dimensional stability) of the cellulose fiber itself are high, so when the cellulose fiber is dispersed in a polymer, the resin composition tends to have high heat resistance, strength and dimensional stability. A high crystallinity is preferred, but from the perspective of production, the preferred upper limit is 99%.
[0348] The crystallinity referred to herein is determined by the following formula based on the Segal method from the diffraction pattern (2θ / deg. is 10 to 30) when the cellulose fiber is cellulose I type crystal (derived from natural cellulose) when the sample is measured by wide-angle X-ray diffraction.
[0349] Crystallinity (%) = ([Diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [Diffraction intensity due to the amorphous state at 2θ / deg. = 18]) / [Diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100
[0350] In addition, regarding the crystallinity, when the cellulose fiber is a cellulose type II crystal (derived from regenerated cellulose), it can be calculated using the following formula based on the absolute peak intensity h0 at 2θ=12.6° of the (110) plane peak belonging to the cellulose type II crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at the plane interval.
[0351] Crystallinity (%) = h1 / h0×100
[0352] As the crystal form of cellulose, there are known types I, II, III, and IV, among which type I and II are particularly common, and type III and IV can be obtained on a laboratory scale, but are not commonly used on an industrial scale. As the cellulose fiber disclosed in the present invention, the structural mobility is relatively high, and since a resin composition having a lower linear expansion coefficient and better strength and elongation during stretching and bending deformation can be obtained by dispersing the cellulose fiber in a resin, a cellulose fiber containing cellulose type I crystals or cellulose type II crystals is preferred, and a cellulose fiber containing cellulose type I crystals and having a crystallinity of 55% or more is more preferred.
[0353] The degree of polymerization of the cellulose fibers is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, and is preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, more preferably 3000 or less.
[0354] The degree of polymerization of the cellulose fibers is preferably within the above range from the viewpoint of processability and development of mechanical properties. From the viewpoint of processability, the degree of polymerization is preferably not too high, and from the viewpoint of development of mechanical properties, it is preferably not too low.
[0355] The degree of polymerization of cellulose fibers refers to the average degree of polymerization measured by the reduced viscosity method using an ethylenediamine copper solution described in the confirmation test (3) of "The Fifteenth Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)".
[0356] In one embodiment, the weight average molecular weight (Mw) of the cellulose fiber is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, so the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminal of the cellulose molecule is the starting point of thermal decomposition, when not only the weight average molecular weight of the cellulose molecule is large, but also the weight average molecular weight is large and the molecular weight distribution width is narrow at the same time, a cellulose fiber with particularly high heat resistance and a resin composition comprising cellulose fiber and a resin can be obtained. With regard to the weight average molecular weight (Mw) of the cellulose fiber, from the aspect of the ease of obtaining the cellulose raw material, for example, it can be 600,000 or less, or 500,000 or less. Regarding the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn), from the aspect of the ease of manufacturing the cellulose fiber, for example, it can be 1.5 or more, or 2 or more. By selecting a cellulose raw material having a Mw corresponding to the purpose, and appropriately performing physical treatment and / or chemical treatment on the cellulose raw material in an appropriate range, Mw can be controlled within the above range. For Mw / Mn, it can also be controlled within the above range by selecting a cellulose raw material having a Mw / Mn corresponding to the purpose, and appropriately performing physical treatment and / or chemical treatment on the cellulose raw material in an appropriate range. In both the control of Mw and the control of Mw / Mn, as the above-mentioned physical treatment, examples can be given of physical treatments based on dry or wet crushing such as microfluidizers, ball mills, disc mills, etc., crushers, homogeneous mixers, high-pressure homogenizers, ultrasonic devices, etc., and physical treatments such as mechanical forces such as impact, shearing, shearing, and friction, and as the above-mentioned chemical treatments, examples can be given of steaming, bleaching, acid treatment, regenerated cellulose, etc.
[0357] The weight average molecular weight and number average molecular weight of the cellulose fibers mentioned herein are values determined by dissolving the cellulose fibers in N,N-dimethylacetamide to which lithium chloride is added and then subjecting the resultant to gel permeation chromatography using N,N-dimethylacetamide as a solvent.
[0358] As a method for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose fibers, hydrolysis treatment and the like can be cited. The amorphous cellulose inside the cellulose is depolymerized by hydrolysis treatment, and the average degree of polymerization is reduced. In addition, at the same time, by hydrolysis treatment, in addition to the amorphous cellulose mentioned above, impurities such as hemicellulose and lignin are also removed, so that the fiber interior becomes porous. As a result, in the process of applying mechanical shear force to cellulose in the kneading process described later, the cellulose is easily subjected to mechanical treatment, and the cellulose is easily refined.
[0359] The alkali-soluble polysaccharides that cellulose fibers may contain include, in addition to hemicellulose, β-cellulose and γ-cellulose. For those skilled in the art, alkali-soluble polysaccharides may be understood as components obtained in the form of alkali-soluble parts of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components from which α-cellulose has been removed from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups, which have poor heat resistance and may lead to decomposition when heated, yellowing during heat aging, and reduction in the strength of cellulose fibers. Therefore, it is preferred that the alkali-soluble polysaccharide content in cellulose fibers is low.
[0360] In one embodiment, from the aspect of obtaining good dispersibility of cellulose fibers, the average content of alkali-soluble polysaccharides in cellulose fibers is preferably 20% by mass or less, or 18% by mass or less, or 15% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less relative to 100% by mass of cellulose fibers. Regarding the above content, from the aspect of the ease of manufacturing of cellulose fibers, it can be 1% by mass or more, or 2% by mass or more, or 3% by mass or more, or 6% by mass or more. In one embodiment, the average content of alkali-soluble polysaccharides in cellulose raw materials can be 13% by mass or less, or 12% by mass or less, or 11% by mass or less, or 8% by mass or less, and most preferably 0% by mass, from the aspect of the ease of obtaining cellulose raw materials, for example, it can be 3% by mass or more, or 6% by mass or more.
[0361] The average content of alkali-soluble polysaccharides can be obtained by the method described in the non-patent literature (Handbook of Wood Science Experiments, edited by the Japan Wood Society, pages 92-97, 2000), which is obtained by subtracting the α-cellulose content from the total cellulose content (Wise method). It should be noted that this method is understood in the art as a method for determining the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for one sample, and the calculated alkali-soluble polysaccharide content is averaged as the average alkali-soluble polysaccharide content.
[0362] In one embodiment, from the perspective of avoiding a decrease in the heat resistance of the cellulose fibers and the discoloration associated therewith, the average content of the acid-insoluble components in the cellulose fibers is preferably 10% by mass or less, or 5% by mass or less, or 3% by mass or less relative to 100% by mass of the cellulose fibers. From the perspective of ease of production of the cellulose fibers, the above content may be 0.1% by mass or more, or 0.2% by mass or more, or 0.3% by mass or more.
[0363] About the average content of acid-insoluble components, the Klason method described in the non-patent literature (Handbook of Wood Science Experiments, Japan Wood Society, pp. 92-97, 2000) is used to quantify the acid-insoluble components. It should be noted that this method is understood as a method for determining the amount of lignin in the art. After stirring the sample in a sulfuric acid solution to dissolve cellulose and hemicellulose, the residue obtained is equivalent to the acid-insoluble components after filtering with glass fiber filter paper. The acid-insoluble component content is calculated by the weight of the acid-insoluble component, and the number average of the acid-insoluble component content calculated for 3 samples is used as the average content of the acid-insoluble component.
[0364] The cellulose fibers may be chemically treated (eg, oxidized or chemically modified using a modifier). For example, micronized cellulose fibers obtained by oxidizing cellulose using 2,2,6,6-tetramethylpiperidin-1-oxyl radicals, followed by washing and mechanical fiberization as described in Cellulose (1998) 5, 153-164 may be used.
[0365] [Hydrophobicization of cellulose fibers]
[0366] Cellulose fiber can be a cellulose fiber (also referred to as chemically modified cellulose fiber in the present disclosure) that has been hydrophobized using a hydrophobizing agent. By hydrophobizing, the hydrogen bonds between the cellulose fibers are weakened, which helps to disperse microscopically, and as a cellulose fiber, its heat resistance is improved, and the deterioration caused by mixing with the resin can be suppressed, and there is an effect that the cellulose fiber is not easy to become the starting point of physical defects. As a hydrophobizing agent (also referred to as a modifying agent in the present disclosure), a compound that reacts with the hydroxyl group of cellulose can be used, and esterifying agents, etherifying agents and silylating agents can be cited. Esterifying agents are particularly preferred. In a preferred embodiment, hydrophobization is acylation using an esterifying agent. As an esterifying agent, acyl halides, acid anhydrides and carboxylic acid vinyl esters are preferred. In a particularly preferred embodiment, hydrophobization is acetylation. Among these esterification reaction agents, from the aspect of reaction efficiency, it is particularly preferred to be selected from at least one of the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate and acetic acid, especially acetic anhydride and vinyl acetate.
[0367] In the case of obtaining hydrophobized cellulose nanofibers, as a method of miniaturizing the natural cellulose raw material and reducing the fiber diameter, there is no particular limitation, and it is preferred to make the processing conditions for opening the fibers (the method of imparting the shear field, the size of the shear field, etc.) more efficient. In particular, by impregnating a fiber opening solution containing an aprotic solvent in a cellulose raw material having a cellulose purity of more than 85% by mass, cellulose swelling occurs in a short time, and the cellulose can be miniaturized by applying only slight stirring and shearing energy. In addition, by adding a cellulose modifier immediately after opening the fibers, hydrophobized cellulose nanofibers can be obtained. From the aspects of generation efficiency and refining efficiency (i.e., high cellulose purification of hydrophobized cellulose nanofibers), and the physical properties of the resin composition, this method is preferred.
[0368] As aprotic solvents, for example, alkyl sulfoxides, alkyl amides, pyrrolidones, etc. can be cited, which can be used alone or in combination of two or more. Among these aprotic solvents, if DMSO (29.8), DMF (26.6), DMAc (27.8), NMP (27.3) (the number in the bracket is the number of donors), etc., especially if DMSO is used, hydrophobic cellulose nanofibers with high thermal decomposition starting temperature can be more effectively produced. Its mechanism of action is not necessarily clear, and it is presumed to be caused by uniform micro-swelling of the fiber raw material in the aprotic solvent.
[0369] The hydrophobicity (modification degree) of cellulose fiber is expressed in the form of the average degree of substitution of hydroxyl groups (the average number of hydroxyl groups substituted per unit of glucose (which is the basic structural unit of cellulose), also referred to as DS). In one embodiment, the DS of chemically modified cellulose fiber is preferably 0.01 or more and 2.0 or less. If DS is 0.01 or more, a resin composition comprising chemically modified cellulose fiber with a high thermal decomposition starting temperature can be obtained. On the other hand, if DS is 2.0 or less, an unmodified cellulose skeleton remains in the chemically modified cellulose fiber, so the chemically modified cellulose fiber has both high tensile strength and dimensional stability derived from cellulose fiber and high thermal decomposition starting temperature derived from chemical modification, and a resin composition comprising the chemically modified cellulose fiber can be obtained. DS is more preferably 0.05 or more, further preferably 0.1 or more, particularly preferably 0.2 or more, most preferably 0.3 or more, more preferably 1.8 or less, further preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less.
[0370] In the reflective infrared absorption spectrum of the hydrophobized cellulose fiber, the peak position of the absorption band varies according to the type of the hydrophobized modifying group. According to the change in the peak position, it can be determined which absorption band the peak is based on, and the identification of the modifying group can be performed. In addition, the modification rate can be calculated based on the peak intensity ratio of the peak derived from the modifying group to the peak derived from the cellulose skeleton.
[0371] When the modification group is an acyl group, the degree of acyl substitution (DS) can be calculated from the reflection infrared absorption spectrum of the esterified cellulose fiber. The absorption band of C=O based on the acyl group appears at 1730 cm -1 The peak of the absorption band of CO based on the cellulose backbone chain appears at 1030 cm -1 The DS of esterified cellulose can be obtained by preparing a correlation diagram between the DS obtained by solid NMR measurement of esterified cellulose and the modification rate (IR index 1030), and using a calibration curve calculated from the correlation diagram. The modification rate is defined by the ratio of the peak intensity of the absorption band based on C=O of the acyl group to the peak intensity of the absorption band of CO of the cellulose backbone chain.
[0372] Degree of substitution DS = 4.13 × IR index (1030)
[0373] It should be noted that when it is difficult to perform appropriate measurements using the above-mentioned reflective infrared absorption spectrum, solid NMR can be used to calculate the area intensity (Inf) of the signal attributed to a carbon atom from the modifying group relative to the total area intensity (Inp) of the signals attributed to carbons C1-C6 of the pyranose ring from cellulose appearing in the range of 50 ppm to 110 ppm, using the following formula.
[0374] DS=(Inf)×6 / (Inp)
[0375] For example, when the modifying group is an acetyl group, the signal of 23 ppm attributed to -CH 3 may be used.
[0376] [Cellulose Nanocrystals]
[0377] Cellulose nanocrystals can be crystalline cellulose remaining after cutting the raw material with pulp or the like and dissolving the amorphous part of cellulose in an acid such as hydrochloric acid or sulfuric acid. The length / diameter ratio (L / D ratio) of the cellulose nanocrystals is less than 30 in one embodiment. The average diameter of the cellulose nanocrystals is less than 1000 nm, preferably less than 500 nm, or less than 200 nm, preferably more than 10 nm, or more than 20 nm, or more than 30 nm in one embodiment. The above-mentioned L / D ratio and average diameter are values measured by the same method as the average fiber diameter of cellulose fibers.
[0378] The L / D of cellulose nanocrystals is less than 30 in one embodiment, preferably less than 25, or less than 20, or less than 15, or less than 10, or less than 5. The lower limit is not particularly limited, and it can be greater than 1. Cellulose nanocrystals can improve the tensile elongation of resin composition. In one embodiment, cellulose whiskers can have the same properties as the above-mentioned properties of cellulose fibers except their size (unmodified or modified forms, etc.).
[0379] [Chitosan fiber, chitosan fiber]
[0380] Chitosan fiber can be a fiber made of the shell of a crustacean or the like as a raw material and having a polymer of acetylglucosamine obtained by separating and purifying the raw material as a main component, i.e., chitosan as a main component. Chitosan fiber is a fiber obtained by deacetylation of chitosan fiber, and can be a fiber having a polymer of glucosamine, i.e., chitosan, as a main component. In one embodiment, the average diameters of chitosan fiber and chitosan fiber are 2 to 1000 nm, preferably 500 nm or less, or 200 nm or less, and preferably 10 nm or more, 20 nm or more, or 30 nm or more.
[0381] In one embodiment, L / D of the chitin fiber and the chitosan fiber is 30 or more, preferably 50 or more, or 100 or more, and in one embodiment, it can be 100,000 or less, or 50,000 or less, or 10,000 or less, or 5,000 or less.
[0382] [Aramid fiber]
[0383] Aramid fiber is a synthetic fiber with aromatic polyamide as the main component, and is roughly divided into para-aramid fiber and meta-aramid fiber according to the structure of the aromatic group. The average diameter of the aramid fiber is 2 to 1000 nm, preferably 500 nm or less, or 200 nm or less, preferably 10 nm or more, or 20 nm or more, or 30 nm or more.
[0384] In one embodiment, L / D of the aramid fiber is 30 or more, preferably 50 or more, or 100 or more, and in one embodiment, may be 100,000 or less, or 50,000 or less, or 10,000 or less, or 5,000 or less.
[0385] The fiber length, fiber diameter, and L / D of organic fibers other than cellulose fibers were measured by the same method as that for cellulose fibers.
[0386] <Polymer>
[0387] The second component includes a polymer in one mode. In one mode, about the polymer in the first component and the polymer in the second component, the molecular structure and / or molecular weight of at least one polymer constituting them are different from each other. About the polymer as the second component, for example, including one or more selected from the group consisting of polyolefin resins, polyamide resins, polyester resins, polyacetal resins, polyphenylene sulfide resins, polyvinyl alcohol resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl chloride resins, polycarbonate resins, polymethyl methacrylate resins, polyurethane resins, fluorine resins, polyacrylonitrile resins, polybutene resins, polyimide resins, polyarylate resins, cellulose resins, polyphenylene ether resins, elastomers and their modified substances (such as modified substances of maleic anhydride, etc.), or can be selected from the group consisting of one or more of them.
[0388] [Polyphenylene ether]
[0389] Polyphenylene ether has a structure represented by the following general formula (1).
[0390] [Chemistry 1]
[0391]
[0392] (In formula (1), R 1 , R 2 , R 3 and R 4 Each is independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halogenated hydrocarbyloxy group in which a halogen atom and an oxygen atom are separated by at least two carbon atoms, and n is an integer greater than 20.
[0393] From the viewpoint of the bending properties of the resin composition and the like, it is advantageous to use polyphenylene ether as the second component.
[0394] In the above formula (1), R 1 , R 2 , R 3 and R 4 Examples of the halogen atom represented by include a fluorine atom, a chlorine atom, a bromine atom and the like, and a chlorine atom and a bromine atom are preferred.
[0395] In the above formula (1), R 1 , R 2 , R 3 and R 4 The "alkyl" represented here means a linear or branched alkyl group having preferably 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms, and examples thereof include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, etc. Methyl and ethyl are preferred, and methyl is more preferred.
[0396] In the above formula (1), R 1 , R 2 , R 3 and R 4 The alkyl group represented may be substituted with one or more substituents at the substitutable position. Examples of such substituents include halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms), alkyl groups having 1 to 6 carbon atoms (e.g., methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl), aryl groups (e.g., phenyl, naphthyl), alkenyl groups (e.g., vinyl, 1-propenyl, 2-propenyl), alkynyl groups (e.g., ethynyl, 1-propynyl, 2-propynyl), aralkyl groups (e.g., benzyl, phenethyl), and alkoxy groups (e.g., methoxy, ethoxy).
[0397] In the above formula (1), n may be 20 or more, 100 or more, or 200 or more, and may be 2000 or less, 1000 or less, or 400 or less.
[0398] The polyphenylene ether is not particularly limited, and known substances can be used. For example, poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), etc. can be mentioned, and polyphenylene ether copolymers of 2,6-dimethylphenol and other phenols (such as 2,3,6-trimethylphenol or 2-methyl-6-butylphenol) can also be used. Among the above, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is more preferred.
[0399] These polyphenylene ethers may be used alone or in combination of two or more.
[0400] The intrinsic viscosity [η] of the polyphenylene ether is preferably 0.1 dl / g or more, or 0.2 dl / g or more, or 0.3 dl / g or more from the perspective of obtaining a high-rigidity resin composition, and is preferably 1.0 dl / g or less, or 0.7 dl / g or less, or 0.6 dl / g or less, or 0.5 dl / g or less from the perspective of imparting good fluidity to the resin composition. The above intrinsic viscosity is a value measured in chloroform at 25°C.
[0401] In one embodiment, at least a portion of the polyphenylene ether may be acid-modified. The acid-modification may be achieved by reacting a modifier (eg, α,β-unsaturated carboxylic acid and derivatives thereof) with the polyphenylene ether.
[0402] Examples of the α,β-unsaturated carboxylic acid include monobasic acids such as (meth)acrylic acid, crotonic acid, isocrotonic acid, furanic acid, pentenoic acid, vinylacetic acid, and angelic acid; dibasic acids such as maleic acid, chloromaleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, and bridged cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (nadic acid); and tribasic acids such as citric acid and aconitic acid.
[0403] As the derivative of α,β-unsaturated carboxylic acid, examples include acid halides, amides, imides, anhydrides, esters, etc. of the above-mentioned α,β-unsaturated carboxylic acids. For example, maleic chloride, acrylamide, maleimide, N-phenylmaleimide, N-methylmaleimide, N-ethylmaleimide, maleic anhydride, itaconic anhydride, glutaconic anhydride, citraconic anhydride, nadic anhydride, aconitic anhydride, methyl (meth)acrylate, monomethyl maleate, dimethyl maleate, diethyl itaconate, dibutyl citrate, glycidyl (meth)acrylate, diglycidyl maleate, etc. Among them, as examples of preferred modifiers, maleic acid, citric acid, itaconic acid, itaconic anhydride, maleic anhydride, and more preferably citric acid and maleic anhydride.
[0404] Regarding the degree of acid modification of the polyphenylene ether, from the perspective of making the second component finely dispersed, it is preferably 0.01% or more, or 0.1% or more, or 0.2% or more, or 0.25% or more, and from the perspective of obtaining the advantages brought about by the use of the polyphenylene ether, it is preferably 10% or less, or 5% or less, or 2% or less, or 1% or less, or 0.7% or less, or 0.6% or less. The polyphenylene ether disclosed in the present invention may be a mixture of two or more polymers with different degrees of acid modification. In this case, the acid modification degree of the entire polyphenylene ether in the resin composition is preferably within the above range. The above acid modification degree is an addition rate calculated based on infrared spectroscopy. When the acidic functional group comes from maleic anhydride, a mixture of polyphenylene ether and maleic anhydride is used, and for the 1790cm -1 After making a calibration curve in advance, the peak of maleic anhydride modified polyphenylene ether at 1790 cm -1 The addition rate was calculated from the peak intensity.
[0405] As examples of the acid modification method of polyphenylene ether, there can be exemplified a method of reacting a modifier with polyphenylene ether in a flowing state (e.g., by melting or dispersion or dissolution in a solvent); a method of reacting a modifier with a powdered polyphenylene ether at a temperature below the glass transition point of the polyphenylene ether in the presence of a modifier; etc. As examples of the method of reacting a modifier with polyphenylene ether in a flowing state, there can be exemplified a method of melt-kneading polyphenylene ether and a modifier at 250° C. to 350° C. for 5 seconds to 30 minutes using a roll mill, a Banbury mixer, an extruder, etc.; a method of dissolving polyphenylene ether in an organic solvent (e.g., toluene, xylene, decalin, tetralin, etc.), then adding a modifier and heating. In addition, as an example of a method for reacting a modifier with a powdered polyphenylene ether, there can be cited a method in which a specified amount of polyphenylene ether and a modifier are added to a stirring device capable of high-speed stirring, and the temperature of the contents is maintained at 160°C to 200°C for at least 30 seconds by shear heat release due to high-speed stirring and / or heat transfer from a jacket.
[0406] The reaction can be carried out in the presence of a free radical initiator. As free radical initiators, organic peroxides (benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, tert-butyl cumyl peroxide, cumene hydroperoxide, 2,5-dimethyl-2,5-di-(tert-butyl peroxide) hexane, 2,5-dimethyl-2,5-di-(tert-butyl peroxide) hexyne-3, etc.), azo compounds (azobisisobutylnitrile, dimethyl azoisobutyrate, etc.). The amount of the free radical initiator used can be, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of the polyphenylene ether.
[0407] In one embodiment, the polyphenylene ether may be a mixture of a polyphenylene ether having an acidic functional group and a polyphenylene ether not having an acidic functional group. Regarding the mixing ratio of the polyphenylene ether having an acidic functional group and the polyphenylene ether not having an acidic functional group, when the total of the two is taken as 100% by mass, from the aspect of obtaining the advantages brought by the polyphenylene ether having an acidic functional group well, it is preferably 10% by mass or more, more preferably 20% by mass or more, further more preferably 30% by mass or more, and most preferably 40% by mass or more. The upper limit is not particularly limited, and substantially all of the polyphenylene ether may be a polyphenylene ether having an acidic functional group, but from the aspect that the fluidity during melting does not cause problems, it is preferably 80% by mass or less.
[0408] The polymer as the second component is an elastomer in one embodiment. In the present disclosure, the elastomer is a substance (specifically, a natural or synthetic polymer substance) that is an elastomer at room temperature (23° C.). The elastomer is advantageous in terms of improving the toughness and elongation (particularly the elongation in a low temperature environment) of the resin composition.
[0409] As specific examples of elastomers, natural rubber, conjugated diene compound polymers, aromatic compound-conjugated diene copolymers, hydrogenated products of aromatic compound-conjugated diene copolymers, polyolefins, polyester elastomers, polyurethane elastomers, polyamide elastomers, elastomers with core-shell structures, etc. can be cited. Among these, aromatic compound-conjugated diene copolymers and hydrogenated products thereof, polyolefins, and elastomers with core-shell structures are preferred from the perspective of the ease of modification reaction of the acidic functional groups described later. As the above-mentioned aromatic compound-conjugated diene copolymers and hydrogenated products thereof, aromatic compound-conjugated diene block copolymers and hydrogenated products thereof are more preferred, and as the above-mentioned polyolefins, copolymers of ethylene and α-olefins are more preferred.
[0410] In one embodiment, the elastomer is one or more selected from the group consisting of ethylene-α-olefin copolymers, block copolymers of aromatic vinyl compounds and conjugated diene compounds, and hydrogenated products of block copolymers of aromatic vinyl compounds and conjugated diene compounds.
[0411] In the present disclosure, the aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block (A) with an aromatic vinyl compound as the main body and a polymer block (B) with a conjugated diene compound as the main body. From the aspect of showing impact strength, the bonding form of each block is preferably a block copolymer of any one of AB type, ABA type, and ABAB type, and ABA type or ABAB type is more preferred.
[0412] In addition, the mass ratio of the aromatic vinyl compound unit to the conjugated diene compound unit in the block copolymer is preferably 10 / 90 to 70 / 30. More preferably 15 / 85 to 55 / 45, most preferably 20 / 80 to 45 / 55. Furthermore, they can also be materials formed by blending copolymers having different mass ratios of two or more aromatic vinyl compounds and conjugated diene compounds. As specific examples of aromatic vinyl compounds, styrene, α-methylstyrene, vinyltoluene, etc. can be cited, and one or more compounds selected from them are used, wherein styrene is particularly preferred.
[0413] Specific examples of conjugated diene compounds include butadiene, isoprene, piperylene, 1,3-pentadiene, etc., and one or more compounds selected from these are used, among which butadiene, isoprene and a combination thereof are preferred, and butadiene is particularly preferred. When butadiene is used as the conjugated diene compound of the block copolymer, as the microstructure of the polybutadiene block portion, from the perspective of suppressing crystallization of the soft segment, the 1,2-vinyl content or the total amount of the 1,2-vinyl content and the 3,4-vinyl content is preferably 5 to 80% on a molar basis, more preferably 10 to 50%, and most preferably 15 to 40%.
[0414] Aromatic compound-conjugated diene block copolymer is a block copolymer composed of a polymer block with an aromatic vinyl compound as the main body and a polymer block with a conjugated diene compound as the main body, and refers to a block copolymer that is substantially not subjected to hydrogenation treatment. The hydrogenated product of the block copolymer of an aromatic vinyl compound and a conjugated diene compound refers to a substance in which the aliphatic double bonds of the polymer block with a diene compound as the main body are controlled to be greater than 0% to 100% by hydrogenating the block copolymer of the above-mentioned aromatic vinyl compound and a conjugated diene compound. From the perspective of suppressing thermal degradation during processing, the hydrogenation rate of the hydrogenated product of the block copolymer is preferably 50% or more, more preferably 80% or more, and most preferably 98% or more, and from the perspective of low-temperature toughness, it is preferably 50% or less, more preferably 20% or less, and most preferably 0% (i.e., a block copolymer of an aromatic vinyl compound and a conjugated diene compound).
[0415] In addition, as the molecular weight of the block copolymer of the aromatic vinyl compound and the conjugated diene compound and its hydrogenated product, the number average molecular weight (Mn) is preferably 10,000 to 500,000, and most preferably 40,000 to 250,000 from the perspective of both impact strength and fluidity. In the present disclosure, unless otherwise specified, the number average molecular weight refers to the value measured by using a gel permeation chromatography apparatus and chloroform as a solvent at a measurement temperature of 40°C and converted to a polystyrene standard.
[0416] These block copolymers of aromatic vinyl compounds and conjugated diene compounds may be used by mixing two or more substances having different bonding forms, substances having different molecular weights, substances having different kinds of aromatic vinyl compounds, substances having different kinds of conjugated diene compounds, substances having different 1,2-vinyl contents or the total amount of 1,2-vinyl contents and 3,4-vinyl contents, substances having different contents of aromatic vinyl compound components, substances having different hydrogenation rates, etc. In a mixture of substances having different hydrogenation rates, the preferred hydrogenation rate of the mixture is as described above.
[0417] In addition, as the polyolefin, an ethylene-α-olefin copolymer can be preferably used from the viewpoint of exhibiting impact resistance. Examples of the monomer copolymerizable with the ethylene unit include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, aliphatic substituted vinyl monomers such as isobutylene, aromatic vinyl monomers such as styrene and substituted styrene, ester vinyl monomers such as vinyl acetate, acrylic acid ester, methacrylic acid ester, glycidyl acrylate, glycidyl methacrylate, hydroxyethyl methacrylate, acrylamide, allylamine, vinyl-p-aminobenzene, nitrogen-containing vinyl monomers such as acrylonitrile, and dienes such as butadiene, cyclopentadiene, 1,4-hexadiene, and isoprene.
[0418] The copolymer is preferably a copolymer of ethylene and one or more α-olefins having 3 to 20 carbon atoms, more preferably a copolymer of ethylene and one or more α-olefins having 3 to 16 carbon atoms, and most preferably a copolymer of ethylene and one or more α-olefins having 3 to 12 carbon atoms. In addition, as for the molecular weight of the ethylene-α-olefin copolymer, from the aspect of exhibiting impact resistance, the number average molecular weight (Mn) measured at 140° C. using a gel permeation chromatography measuring apparatus and 1,2,4-trichlorobenzene as a solvent with a polystyrene standard sample is preferably 10,000 or more, more preferably 10,000 to 100,000, and even more preferably 20,000 to 60,000. In addition, from the aspect of achieving both fluidity and impact resistance, the molecular weight distribution (weight average molecular weight / number average molecular weight: Mw / Mn) is preferably 3 or less, and even more preferably 1.8 to 2.7.
[0419] In addition, from the viewpoint of handling properties during processing, the content of ethylene units in the ethylene-α-olefin copolymer is preferably 30 to 95% by mass based on the total amount of the ethylene-α-olefin copolymer.
[0420] These preferred ethylene-α-olefin copolymers can be produced by the production methods described in, for example, JP-B-4-12283, JP-A-60-35006, JP-A-60-35007, JP-A-60-35008, JP-A-5-155930, JP-A-3-163088, U.S. Pat. No. 5,272,236, and the like.
[0421] In the present disclosure, as an elastomer having a core-shell structure, there can be cited a core-shell type elastomer having a core of granular rubber and a shell of a glassy graft layer formed outside the core. As for the rubber component as the core, butadiene rubber, acrylic rubber, silicone-acrylic composite rubber, etc. can be preferably used. In addition,
[0422] As the shell, preferably a glassy polymer such as styrene resin, acrylonitrile-styrene copolymer, acrylic resin, etc. For example, when the first component comprises polyamide, from the aspect of compatibility with polyamide, an elastomer having a core-shell structure having a core of butadiene rubber and a shell of acrylic resin can be preferably used.
[0423] In one embodiment, at least a portion of the elastomer has an acidic functional group. In the present disclosure, the elastomer having an acidic functional group means that the acidic functional group is added to the molecular skeleton of the elastomer by chemical bonding. In addition, in the present disclosure, the acidic functional group refers to a functional group that can react with a basic functional group, etc., and specific examples thereof include a hydroxyl group, a carboxyl group, a carboxylate group, a sulfonic group, an anhydride group, etc.
[0424] From the aspect of compatibility with the second polymer having an acidic functional group or the polyphenylene ether having an acidic functional group, the amount of the acidic functional group added to the elastomer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more, based on 100% by mass of the elastomer, and preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less. It should be noted that the number of acidic functional groups is a value obtained by measuring a calibration curve sample pre-mixed with an acidic substance using an infrared absorption spectrometer, and measuring the sample based on a calibration curve prepared using the characteristic absorption band of the acid, and the value obtained is the number of the acidic functional groups.
[0425] Examples of the elastomer having an acidic functional group include an elastomer having a core-shell structure having a layer as a shell formed using acrylic acid or the like as a copolymer component; an elastomer which is a modified product obtained by grafting an α,β-unsaturated dicarboxylic acid or a derivative thereof onto an ethylene-α-olefin copolymer, a polyolefin, an aromatic compound-conjugated diene copolymer or an aromatic compound-conjugated diene copolymer hydrogenated product containing acrylic acid or the like as a monomer in the presence or absence of a peroxide; and the like.
[0426] In a preferred embodiment, the elastomer is an anhydride-modified elastomer.
[0427] Among these, more preferred are modified products obtained by grafting α,β-unsaturated dicarboxylic acids or their derivatives onto polyolefins, aromatic compound-conjugated diene copolymers or aromatic compound-conjugated diene copolymer hydrogenates in the presence or absence of peroxides, and particularly preferred are modified products obtained by grafting α,β-unsaturated dicarboxylic acids and their derivatives onto ethylene-α-olefin copolymers or aromatic compound-conjugated diene block copolymer hydrogenates in the presence or absence of peroxides.
[0428] Specific examples of the α,β-unsaturated dicarboxylic acid and its derivatives include maleic acid, fumaric acid, maleic anhydride and fumaric anhydride. Among these, maleic anhydride is particularly preferred.
[0429] In one embodiment, the elastomer can be a mixture of an elastomer with an acidic functional group and an elastomer without an acidic functional group. Regarding the mixing ratio of an elastomer with an acidic functional group and an elastomer without an acidic functional group, from the aspect of maintaining the high toughness and physical stability of the resin combination well, when the total of the two is 100% by mass, the elastomer with an acidic functional group is preferably more than 10% by mass, more preferably more than 20% by mass, further more preferably more than 30% by mass, and most preferably more than 40% by mass. The upper limit is not particularly limited, and substantially all elastomers can be elastomers with an acidic functional group, but from the aspect that fluidity does not cause problems, it is preferably less than 80% by mass.
[0430] When the second component includes a polymer or is a polymer, the polymer can form a granular dispersed phase (dispersed particles) in the resin composition. In this case, the dispersed particle size is preferably less than 3 μm, more preferably less than 2 μm, and most preferably less than 1 μm in terms of number average particle size. The lower limit is not particularly limited, for example, 0.01 μm. From the aspect of high toughness and physical property stability, it is preferably within the above range.
[0431] In resin combination, relative to the overall 100 mass % of resin combination, the amount of the polymer as the second component is preferably 0.1 mass % or more, or 0.5 mass % or more, or 1 mass % or more, or 3 mass % or more, preferably 30 mass % or less, or 25 mass % or less, or 20 mass % or less, or 15 mass % or less. When the amount of the polymer is the above-mentioned range, it is preferred from the aspect of high tensile elongation, high flexural modulus, low thermal expansion coefficient and / or good physical property stability.
[0432] "Additional ingredients"
[0433] In the resin composition of forms A to C, additional components may be further included as needed to improve their performance. As additional components, the following may be mentioned: dispersant; filler components other than organic fibers; bulking agents; plasticizers; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, animal glue, and casein; inorganic compounds such as zeolite, ceramics, talc, silicon oxide, metal oxides, and metal powders; colorants; fragrances; pigments; flow regulators; leveling agents; conductive agents; antioxidants; antistatic agents; ultraviolet absorbers; ultraviolet dispersants; deodorants, etc. The content ratio of the optional additional components in the resin composition can be appropriately selected within the range that does not impair the desired effect of the present invention, for example, it can be 0.01 to 50% by mass, or 0.1 to 30% by mass.
[0434] As a dispersant, a compound that can react or interact with the second component is preferred. For example, when the second component has a hydrogen bond forming structure (such as a hydroxyl group, etc.), as a dispersant, a compound that can react or form a hydrogen bond with the hydrogen bond forming structure is preferred. Preferred examples of dispersants are one or more selected from the group consisting of cellulose derivatives, polyalkylene oxides, amides and amines. Among them, in the case where the second component contains cellulose, since the cellulose derivative is a cellulose-based substance, it has a high affinity with the cellulose. On the other hand, since it is also a thermoplastic resin, the dispersion stability of cellulose in the resin composition is improved. It is preferred. As a dispersant, a dispersant having a boiling point higher than that of water is preferred. It should be noted that a boiling point higher than water refers to a boiling point higher than the boiling point at each pressure in the vapor pressure curve of water (for example, 100°C at 1 atmosphere).
[0435] In the resin composition, the amount of the dispersant is preferably 1 part by mass or more, or 5 parts by mass or more, or 10 parts by mass or more, or 20 parts by mass or more relative to 100 parts by mass of the second component, from the perspective of good dispersion of the second component and, when the second component contains organic fibers, from the perspective of forming a network between the fibers, and is preferably 500 parts by mass or less, or 300 parts by mass or less, or 200 parts by mass or less from the perspective of reducing performance variation of the resin composition.
[0436] 《Characteristics of resin composition》
[0437] The resin composition obtained by the methods of Modes A to C can have the following properties.
[0438] <Average Fiber Diameter and L / D of Organic Fibers in Resin Composition>
[0439] In one embodiment, the average fiber diameter of the organic fibers in the resin composition can be less than 1000nm, or less than 500nm, or less than 450nm, or less than 400nm, or less than 350nm, or less than 300nm, or less than 250nm, or less than 200nm, or less than 150nm, or less than 100nm, and can be more than 2nm, or more than 4nm, or more than 5nm, or more than 10nm, or more than 15nm, or more than 20nm, or more than 30nm, or more than 40nm, or more than 50nm, or more than 100nm.
[0440] Regarding the average fiber length / average fiber diameter ratio (L / D) of the organic fibers in the resin composition, in one embodiment, it can be greater than 30, or greater than 50, or greater than 80, or greater than 100, and in one embodiment, it can be less than 5000, or less than 4000, or less than 3000.
[0441] <Thixotropic Index>
[0442] In the resin composition obtained by the method of methods A to C, the second component can be uniformly dispersed. The thixotropic index of the resin composition is an indicator of the dispersion uniformity of the second component, and the thixotropic index increases if the dispersion uniformity is high. This phenomenon may be significant when the second component contains organic fibers, especially cellulose fibers. Regarding the thixotropic index of the resin composition, it is preferably 2 or more, or 3 or more, or 4 or more from the perspective of good dispersion uniformity of the second component, and is preferably 10 or less, or 9 or less, or 8 or less from the perspective of ease of manufacturing the resin composition. It should be noted that the above-mentioned thixotropic index is obtained by using a dynamic viscoelasticity measuring device at a temperature of the melting point of the thermoplastic resin contained in the resin composition (when there are two or more thermoplastic resins, the melting point of the highest temperature side) + 25°C. The shear rate is 1 second. -1 The viscosity at shear rate is 10 seconds -1 The obtained value is taken as the thixotropic index.
[0443] <Tensile elongation>
[0444] In one embodiment, the tensile elongation of the resin composition measured in accordance with ISO527-1 may be 2% or more, 3% or more, or 5% or more, and may be 500% or less, 300% or less, or 100% or less from the perspective of ease of production of the resin composition.
[0445] <Flexural modulus>
[0446] In one embodiment, the flexural modulus of the resin composition measured in accordance with ISO178 may be 1 GPa or more, 2 GPa or more, or 3 GPa or more, and may be 20 GPa or less, 15 GPa or less, or 10 GPa or less from the perspective of ease of production of the resin composition.
[0447] <Tensile Strength>
[0448] In one embodiment, the tensile strength of the resin composition measured in accordance with ISO527-1 may be 10 MPa or more, 20 MPa or more, or 50 MPa or more, and may be 300 MPa or less, 250 MPa or less, or 150 MPa or less from the perspective of ease of production of the resin composition.
[0449] <Linear Thermal Expansion Coefficient>
[0450] In one embodiment, the coefficient of linear thermal expansion of the resin composition measured by thermomechanical analysis (TMA) in accordance with ISO11359-2 in the temperature range of 20°C to 100°C may be 140 ppm / K or less, or 100 ppm / K or less, or 70 ppm / K or less, or 60 ppm / K or less, or 50 ppm / K or less, or 45 ppm / K or less, or 40 ppm / K or less, or 35 ppm / K or less, and from the perspective of ease of production of the resin composition, may be 5 ppm / K or more, or 10 ppm / K or more.
[0451] 《Application of resin composition》
[0452] The resin compositions of forms A to C are useful as substitutes for steel plates, fiber reinforced plastics (e.g., carbon fiber reinforced plastics, glass fiber reinforced plastics, etc.), resin composites containing inorganic fillers, etc. Preferred uses of the resin compositions include industrial machinery parts, general machinery parts, automobile, railway, vehicle, ship, and aerospace related parts, electronic and electrical parts, construction and civil engineering materials, daily necessities, sports and leisure products, housing parts for wind power generation, and container and packaging parts.
[0453] Example
[0454] The present invention will be further described below with reference to examples, but the present invention is not limited to the following examples.
[0455] (1) Example A (Example of Aspect A of the Present Disclosure)
[0456] Evaluation Method
[0457] <Gap between the inner wall of the barrel and the screw>
[0458] It is obtained by direct measurement using a vernier caliper. Specifically, in the flow path of the mixture, the gap between the inner wall of the barrel and the screw at the widest flow path is measured. At the seal, the gap between the outer edge of the seal and the inner wall of the barrel is measured, and at the kneading disk and the thread, the gap between their outer edges in the short axis direction and the inner wall of the barrel is measured.
[0459] <Tensile elongation and flexural modulus of mixture and resin composition>
[0460] The obtained mixture or resin composition was molded into a multi-purpose test piece according to ISO 294-3 using an injection molding machine under conditions according to JIS K6920-2. For the multi-purpose test piece, the tensile elongation at break was measured according to ISO 527, and the flexural modulus was measured according to ISO 178. It should be noted that since the polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.
[0461] <Charpy Impact Strength of Resin Composition>
[0462] Using the multipurpose test piece prepared in the same manner as above, the Charpy impact strength was measured by the method described in ISO179-1.
[0463] <Average fiber length, average fiber diameter and L / D of organic fibers used and organic fibers in the resin composition>
[0464] The wet cake was diluted with tert-butyl alcohol to 0.01% by mass, dispersed using a high shear homogenizer (manufactured by IKA, trade name "ULTRA-TURRAX T18") at a rotation speed of 25,000 rpm for 5 minutes, poured onto mica, and air-dried before measurement using a high-resolution scanning microscope. The magnification was adjusted so that at least 100 organic fibers were observed, and the length (L), major diameter (D) and ratio of 100 randomly selected organic fibers were obtained, and the arithmetic average of the 100 organic fibers was calculated.
[0465] It should be noted that for the organic fibers in the resin composition, when the polymer is polyamide, the resin component is dissolved in hexafluoroisopropanol, and when the polymer is polypropylene, the resin component is dissolved in xylene, the organic fibers are separated, and after being fully washed with the above-mentioned solvent, they are replaced with tert-butyl alcohol and the obtained wet cake is used.
[0466] <Average particle size of the dried organic fiber used>
[0467] The d50 particle size was measured using a powder tester, model: PT-X, manufactured by Hosokawa Micron Co., Ltd.
[0468] <Weight Average Molecular Weight (Mw), Number Average Molecular Weight (Mn), and Mw / Mn Ratio of Cellulose Fiber and Chitosan Fiber>
[0469] [Production of porous sheet]
[0470] First, the wet cake is added to tert-butyl alcohol and then dispersed with a mixer until the agglomerates disappear. The organic fiber solid content weight is 0.5 g, and the concentration is adjusted to 0.5% by mass. 100 g of the obtained tert-butyl alcohol dispersion is filtered on filter paper, dried at 150°C, and then the filter paper is peeled off to obtain a sheet. The sheet is 10 g / m 2 A sheet having an air permeability resistance of 100 sec / 100 ml or less and a sheet basis weight of 100 Å was used as a porous sheet and was used as a measurement sample.
[0471] The basis weight W (g / m 2 ) was measured, and the air permeability resistance R (sec / 100ml) was measured using a Wangyan air permeability resistance tester (manufactured by Asahi Seiko Co., Ltd., model EG01). At this time, the following formula was used to calculate the air permeability resistance R (sec / 100ml) per 10g / m 2 The value of basis weight.
[0472] Every 10g / m 2 Air permeability resistance of basis weight (sec / 100ml) = R / W×10
[0473] [Measurement]
[0474] Weigh 0.88g of the porous sheet, cut it into small pieces with scissors, stir it gently, then add 20mL of pure water and let it stand for 1 day. Then separate the water and solid components by centrifugation. Then add 20mL of acetone, stir it gently and let it stand for 1 day. Then separate the acetone and solid components by centrifugation. Then add 20mL of N,N-dimethylacetamide, stir it gently and let it stand for 1 day. After separating N,N-dimethylacetamide and solid components by centrifugation again, add 20mL of N,N-dimethylacetamide, stir it gently and let it stand for 1 day. Separate N,N-dimethylacetamide and solid components by centrifugation, add 19.2g of N,N-dimethylacetamide solution prepared in a solution with 8% by mass of lithium chloride to the solid components, stir it with a stirrer, and visually confirm the dissolution. The solution in which the organic fiber is dissolved is filtered with a 0.45μm filter, and the filtrate is used as a sample for gel permeation chromatography. The device and measurement conditions used are as follows.
[0475] Device: Tosoh HLC-8120
[0476] Column: TSKgel SuperAWM-H (6.0mmI.D.×15cm)×2
[0477] Detector: RI detector
[0478] Eluent: N,N-dimethylacetamide (lithium chloride 0.2%)
[0479] Flow rate: 0.6mL / min
[0480] Calibration curve: Pullulan conversion
[0481] <Crystallinity of cellulose fibers>
[0482] The porous sheet was subjected to X-ray diffraction measurement, and the crystallinity was calculated according to the following formula.
[0483] Crystallinity (%) = [I (200) -I (amorphous) ] / I (200) ×100
[0484] I (200) : Diffraction peak intensity of cellulose type I crystal based on the 200 plane (2θ=22.5°)
[0485] I (amorphous) : The halo peak intensity of cellulose type I crystal based on amorphous cellulose is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200-degree plane (2θ=18.0°).
[0486] (X-ray diffraction measurement conditions)
[0487] Device: MiniFlex (manufactured by Rigaku Co., Ltd.)
[0488] Operating axis: 2θ / θ
[0489] Radiation source: CuKα
[0490] Determination method: continuous
[0491] Voltage: 40kV
[0492] Current: 15mA
[0493] Starting angle: 2θ = 5°
[0494] End angle: 2θ = 30°
[0495] Sampling width: 0.020°
[0496] Scanning speed: 2.0° / min
[0497] Sample: Paste a porous sheet on the sample holder
[0498] <Average Alkali-Soluble Polysaccharide Content of Cellulose Fiber>
[0499] The alkali-soluble polysaccharide content was determined by subtracting the α-cellulose content from the total cellulose content (Wise method) using the method described in the non-patent literature (Handbook of Wood Science Experiments, edited by the Japan Wood Society, pages 92-97, 2000) for cellulose. The alkali-soluble polysaccharide content was calculated three times for one sample, and the calculated alkali-soluble polysaccharide contents were averaged as the average alkali-soluble polysaccharide content of the cellulose.
[0500] <Degree of Substitution (DS) of Cellulose Fiber>
[0501] The infrared spectra were measured at five locations of the porous sheet by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Corporation). The infrared spectroscopic measurement was performed under the following conditions.
[0502] Number of points: 64 times,
[0503] Wave number resolution: 4cm -1 ,
[0504] Measurement wave number range: 4000~600cm -1 ,
[0505] ATR crystal: diamond,
[0506] Angle of incidence: 45°
[0507] The IR index was calculated from the obtained IR spectrum according to the following formula (1).
[0508] IR index = H1730 / H1030···(1)
[0509] Where H1730 and H1030 are 1730cm -1 、1030cm -1 The absorbance of the absorption band of the CO stretching vibration of the cellulose backbone chain is -1 With 1500cm -1 Line and link 800cm -1 With 1500cm -1 The line is taken as the baseline, and the baseline is set as the absorbance when the absorbance is 0.
[0510] Thereafter, the average degree of substitution at each measurement position was calculated from the IR index according to the following formula (2), and the average value was defined as DS.
[0511] DS = 4.13 × IR index (2)
[0512] <Content of Particles Having a Particle Size of 50 μm or More in the Mixture and the Resin Composition>
[0513] Using an injection molding machine, a multi-purpose test piece according to ISO294-3 was molded from the mixture or resin composition under conditions according to JIS K6920-2. A sample of about 2 mm square size was cut from the test piece, and the coagulation was analyzed using an X-CT (X-ray CT device) (manufactured by Bruker Japan, Skyscan 1272). The measurement conditions are as follows.
[0514] Tube voltage: 40kV
[0515] Tube current: 100μA
[0516] Pixel resolution: 1.2μm
[0517] Detector pixel count: 2452×1640 pixels
[0518] Number of points: 4 times
[0519] Determination angle step: 0.2 degrees
[0520] Scanning range: 0-180 degrees
[0521] It should be noted that, for the measured data, a Kuwahara filter is applied between two pixels in the 3D direction to perform smoothing processing to improve the image quality.
[0522] The 3D data thus obtained is automatically binarized using triangulation to extract pixels containing only aggregates. The spherical equivalent volume in the aggregate is (4 / 3)×π×25 3 μm 3 The content (volume %) of particles with a particle size of 50 μm or more in the mixture or resin composition is calculated by taking the ratio of the total sum of pixels of the above agglomerates to the total sum of pixels of the entire observation range, and the content (volume %) of particles with a particle size of 50 μm or more is divided by the total content (volume %) of organic fibers calculated from the mixing amount of organic fibers in the mixture or resin composition. The value thus obtained is regarded as the content (mass %) of particles with a particle size of 50 μm or more in the organic fibers.
[0523] <Particle Diameter of Dispersed Phase in Resin Composition>
[0524] The particle size of the dispersed phase is measured by observing the cross section of the resin composition using a scanning electron microscope. The styrene-based thermoplastic elastomer is dyed by immersing it in an aqueous solution of ruthenium tetroxide. The polyamide resin is dyed by immersing it in an aqueous solution of phosphotungstic acid.
[0525] Materials used
[0526] <1st ingredient>
[0527] Polyamide 6 (PA6): (Ube Industries: 1013B)
[0528] Polypropylene (PP): (Made by PRIME POLYMER: J105G)
[0529] Polyacetal (POM): (Made by Asahi Kasei: HC450)
[0530] <Second ingredient>
[0531] [Acid-modified polyphenylene ether (m-PPE)]
[0532] Made by Asahi Kasei: R4919
[0533] [Styrene-ethylene-butadiene-styrene copolymer (SEBS)]
[0534] Made by Asahi Kasei: Tuftec H1052
[0535] [CNF-A]
[0536] As the CNF-A cake, commercially available Celish KY100G (manufactured by Daicel Finechem) was used.
[0537] [CNF-B] (acetylated CNF)
[0538] A single screw mixer (IMEX DKV-1 1 part by mass of cotton linter pulp was stirred in 30 parts by mass of dimethyl sulfoxide (DMSO) at 500 rpm at room temperature for 1 hour. Then, the mixture was fed into a bead mill (NVM-1.5 manufactured by IMEX) using a hose pump and circulated for 180 minutes using only DMSO to obtain slurry S1 (DMSO solvent) with a solid content ratio of 3.2% by mass as fine cellulose fiber slurry.
[0539] During the circulation operation, the rotation speed of the bead mill was 2500 rpm and the peripheral speed was 12 m / s. The beads used were made of zirconium oxide. The filling rate was 70% (the slit gap of the bead mill was 0.6 mm). In addition, during the circulation operation, the slurry temperature was controlled to 40° C. using a cooler in order to absorb heat generated by friction.
[0540] After the slurry S1 was placed in an explosion-proof dispersion tank, 3.2 parts by mass of vinyl acetate and 0.49 parts by mass of sodium bicarbonate were added, the temperature in the tank was adjusted to 50°C, and stirring was performed for 120 minutes to obtain a slurry having a solid content ratio of 2.9% by mass (DMSO solvent).
[0541] In order to stop the reaction, 30 parts by mass of pure water was added and stirred thoroughly, and then placed in a dehydrator for concentration. The obtained wet cake was dispersed again in 30 parts by mass of pure water, stirred and concentrated, and the washing operation was repeated a total of 5 times to remove unreacted reagents and solvents, thereby obtaining 10 parts by mass of acetylated fine cellulose fiber cake (CNF-B cake) (water solvent) with a solid content ratio of 10%. A porous sheet was made from the cake, and the acyl substitution degree (DS) was calculated, and the result was DS=1.0.
[0542] [CNF-C] (CNF treated with a disc refiner)
[0543] 3 parts by mass of cottonseed linter pulp was immersed in 27 parts by mass of water and heat treated at 130°C for 4 hours in an autoclave. The swollen pulp obtained was washed with water to obtain a refined pulp (30 parts by mass) containing water. Then, 170 parts by mass of water was added to 30 parts by mass of the refined pulp containing water, and the pulp was dispersed in water (solid content ratio 1.5% by mass). As a disc refiner device, an SDR14 type Lab-Refiner (pressurized DISK type) manufactured by Aikawa Iron Works Co., Ltd. was used, and the gap between the discs was 1 mm. The water dispersion was subjected to a beating treatment for 20 minutes. Thereafter, the mixture was concentrated to a solid content ratio of 10% by mass using a dehydrator to obtain a CNF-C cake (water solvent).
[0544] [CNF-D] (CNF-C is further subjected to fiber opening treatment using a high-pressure homogenizer)
[0545] The CNF-C cake was thoroughly beaten under the condition that the gap was reduced to a level close to zero, and a beating water dispersion (solid content concentration: 1.5 mass %) was obtained. The obtained beating water dispersion was directly subjected to 15 micronization treatments at an operating pressure of 100 MPa using a high-pressure homogenizer (NSO15H manufactured by Niro Soavi (Italy)) to obtain a cellulose fiber slurry (solid content concentration: 1.5 mass %). Afterwards, a dehydrator was used to concentrate the solid content ratio to 10 mass %, and a CNF-D cake (water solvent) was obtained.
[0546] [CNF-E] (acetylated CNF)
[0547] The same method as CNF-B was used to produce the product except that the reaction time was changed to 60 minutes. A porous sheet was prepared from the cake, and the degree of acyl substitution (DS) was determined to be DS=0.5.
[0548] [Cellulose Nanocrystals]
[0549] Ceolus FD-301 (manufactured by Asahi Kasei Co., Ltd.) was used.
[0550] [Chitosan fiber]
[0551] Binfis Efo-08002 (manufactured by Sugino Machine) was used.
[0552] [Aramid fiber]
[0553] Tiara KY400S (manufactured by Daicel Finechem) was used.
[0554] Table 1 shows the properties of the organic fibers.
[0555] <Dispersant>
[0556] Polyoxyethylene-polyoxypropylene copolymer (PEG-PPG) (manufactured by Sanyo Chemical: GL-3000)
[0557] 《Mixing method》
[0558] <Extruder Screw Structure>
[0559] As shown in Table 2, the design includes high load zone 1, high load zone 2, high load zone 3 and screws 1 to 6 in the distribution mixing zone. The design is to arrange a mixing element composed of any one of a split-flow screw, a notched screw, a kneading disk, an eccentric multi-strip disk, and an eccentric multi-strip screw in the front half of the high load zone, and to arrange a seal ring with a predetermined gap downstream to block the mixed material. As for the distribution mixing zone, two neutral kneading disks and one reverse screw are arranged in the order of the barrel 11.
[0560] <Mixed Operation>
[0561] [Example A1]
[0562] The preparation of a dried cellulose fiber body and the mixing of the dried cellulose fiber body and a resin are performed according to the following steps to produce a resin composition.
[0563] (Manufacturing of Dried Cellulose Fibers)
[0564] A dispersant is added to a cellulose fiber cake (10% by weight of solid content) in an amount of 43 parts by weight relative to 100 parts by weight of cellulose solid content, and the mixture is stirred thoroughly to obtain a cellulose fiber cake mixed with a dispersant. The cake is put into a drying device as a raw material and dried at a specified shear rate, vacuum degree, and heating temperature (jacket temperature or hot air temperature). The moisture content is measured using an infrared heating moisture meter (MX-50 (manufactured by A&D)), and the time when the moisture content reaches 7% by weight or less (93% by weight or more of solid content) is taken as the end point of drying. The conditions are as follows.
[0565] Planetary mixer (PM)
[0566] Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type)
[0567] Conditions: The pressure was reduced to -90 kPa using a vacuum pump while stirring at 307 rpm at a jacket temperature of 60°C. Drying under reduced pressure was performed until the product temperature reached 50°C.
[0568] As the gap, the minimum distance between the hook-shaped paddle (diameter 100 mm) and the jacket was measured.
[0569] The drying time in this condition is 180 minutes.
[0570] Regarding the drying temperature, the surface temperature of the jacket was measured at three points, and the average value was taken as the drying temperature.
[0571] (Dispersion Mixing)
[0572] Polyamide 6 was fed into the extruder at 2 kg / h, and dried cellulose fibers were fed into the extruder at 2.86 kg / h (2 kg / h as cellulose), and heated and melt-kneaded in a dispersive mixing zone to obtain a dispersed mixture.
[0573] (Distribution Mix)
[0574] Polyamide 6 was added to the dispersed mixture at 4.86 kg / h by side feeding at 15.14 kg / h, and then heated and melt-kneaded in a distribution mixing zone to obtain a resin composition. The obtained resin composition was processed into pellets using a pelletizer. As extrusion characteristics, the case where the screen was clogged within 1 hour after the extruder started operating during the extrusion process was recorded as "poor" operation stability, and the case where there was no clogging was recorded as "good" operation stability.
[0575] [Examples A2 to A19, Comparative Examples A1 to A3]
[0576] A resin composition was produced by the same procedure as in Example A1 except that the composition of the resin composition and the setting conditions of the extruder were changed as shown in Tables 3 to 5, and various evaluations were performed. The results are shown in Tables 3 to 5.
[0577] [Table 1]
[0578]
[0579] [Table 2]
[0580]
[0581] [Table 3]
[0582]
[0583]
[0584] [Table 4]
[0585]
[0586]
[0587] [Table 5]
[0588]
[0589] (2) Example B (Example of embodiment B of the present disclosure)
[0590] Evaluation Method
[0591] <Gap between the inner wall of the barrel and the screw>
[0592] The measurement was carried out in the same manner as in Example A.
[0593] <Mixture filling ratio>
[0594] When extruding, the rotation of the screw and the supply of raw materials are suddenly stopped, the screw is pulled out, and the mixture adhering to the screw surface is collected and measured, and the volume filled with the mixture is calculated by dividing it by the density of the mixture. Then, the volume filled with the mixture is divided by the volume of the space described below to calculate the filling rate of the mixture.
[0595] <Space Volume Ratio>
[0596] The space volume was calculated by subtracting the screw volume (the total of the element volume and the shaft volume) from the barrel volume of the extruder, and the space volume ratio was calculated by dividing the space volume by the barrel volume.
[0597] <area length>
[0598] The total length of the screw elements constituting the dispersive mixing zone and the distributive mixing zone was taken as the zone length.
[0599] <Tensile elongation and flexural modulus of mixture and resin composition>
[0600] The obtained mixture or resin composition was molded into a multi-purpose test piece according to ISO 294-3 using an injection molding machine under conditions according to JIS K6920-2. For the multi-purpose test piece, the tensile elongation at break was measured according to ISO 527-1, and the flexural modulus was measured according to ISO 178. It should be noted that the polyamide resin changes due to moisture absorption, so it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.
[0601] <Content of Particles Having a Particle Size of 50 μm or More in the Mixture and the Resin Composition>
[0602] The measurement was carried out in the same manner as in Example A.
[0603] <Average fiber diameter and L / D of organic fibers used and organic fibers in the resin composition>
[0604] The measurement was carried out in the same manner as in Example A.
[0605] <Weight Average Molecular Weight (Mw), Number Average Molecular Weight (Mn), and Mw / Mn Ratio of Cellulose Fiber and Chitosan Fiber>
[0606] The measurement was carried out in the same manner as in Example A.
[0607] <Crystallinity of cellulose fibers>
[0608] In the same manner as in Example A, a porous sheet was prepared and measured.
[0609] <Average Alkali-Soluble Polysaccharide Content of Cellulose Fiber>
[0610] The measurement was carried out in the same manner as in Example A.
[0611] <Degree of Substitution (DS) of Cellulose Fiber>
[0612] The measurement was carried out in the same manner as in Example A.
[0613] Materials used
[0614] The same materials as in Example A were used.
[0615] 《Mixing method》
[0616] [Extruder Configuration]
[0617] The kneading was carried out using a twin-screw extruder (OMEGA30H manufactured by STEER, L / D=72) with 15 barrel sections. It should be noted that in the barrel 14, an exhaust port was provided at the upper part of the barrel to enable vacuum suction. A 50-mesh screen was installed between the die joint and the die head.
[0618] <Extruder Screw Structure>
[0619] As shown in Table 6, the screws 1 to 5 are designed and arranged with the first dispersive mixing zone, the second dispersive mixing zone, and the distribution mixing zone. The first dispersive mixing zone and the second dispersive mixing zone are respectively designed to be arranged with a mixing element composed of any one of a split-flow screw, a notched screw, a kneading disk, an eccentric multi-strip disk, and an eccentric multi-strip screw in the front half, and a seal ring and / or a reverse screw are combined in the rear half to retain the mixed material. As for the distribution mixing zone, two neutral kneading disks are arranged in the barrel 11, followed by a reverse screw.
[0620] <Mixed Operation>
[0621] [Example B1]
[0622] The preparation of a dried cellulose fiber body and the mixing of the dried cellulose fiber body and a resin were carried out in the following order to produce a resin composition.
[0623] (Manufacturing of Dried Cellulose Fibers)
[0624] A dispersant is added to a cellulose fiber cake (10% by weight of solid content) in an amount of 43 parts by weight relative to 100 parts by weight of cellulose solid content, and the mixture is stirred thoroughly to obtain a cellulose fiber cake mixed with a dispersant. It is put into a drying device as a raw material and dried at a specified shear rate, vacuum degree, and heating temperature (jacket temperature or hot air temperature). The moisture content is measured using an infrared heating moisture meter (MX-50 (manufactured by A&D)), and the time when the moisture content reaches 7% by weight or less (the solid content reaches 93% or more) is taken as the end point of drying. The conditions are as follows. It should be noted that after the dried cellulose fiber is loaded on agar, an X-CT analysis is performed using the above method, and the content of particles with a particle size of 50 μm or more formed by the aggregation of cellulose nanofibers exceeds 50% by weight.
[0625] Planetary mixer (PM)
[0626] Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type)
[0627] Conditions: The pressure was reduced to -90 kPa using a vacuum pump while stirring at 307 rpm at a jacket temperature of 60°C. Drying under reduced pressure was performed until the product temperature reached 50°C.
[0628] As the gap, the minimum distance between the hook-shaped paddle (diameter 100 mm) and the jacket was measured.
[0629] The drying time in this condition is 180 minutes.
[0630] Regarding the drying temperature, the surface temperature of the jacket was measured at three points, and the average value was taken as the drying temperature.
[0631] (Dispersion Mixing)
[0632] Polyamide 6 was fed into the extruder at 2 kg / h, and a dried cellulose fiber was fed into the extruder at 2.86 kg / h (2 kg / h in terms of cellulose), and heated and melt-kneaded in the first dispersing and mixing zone to obtain a first dispersed mixture. Subsequently, heated and melt-kneaded in the second dispersing and mixing zone to obtain a second dispersed mixture.
[0633] (Distribution Mix)
[0634] Polyamide 6 was added to the second dispersed mixture 4.86 kg / h by side feeding at 15.14 kg / h, and then heated and melted in a distribution mixing zone to obtain a resin composition. The obtained resin composition was processed into pellets using a pelletizer. As extrusion characteristics, the operation stability was recorded as "poor" if the screen was blocked within 1 hour after the extruder started to operate during the extrusion process, and the operation stability was recorded as "good" if there was no blockage.
[0635] [Examples B2 to B7, Comparative Example B1]
[0636] A resin composition was produced by the same procedure as in Example B1 except that the composition of the resin composition and the setting conditions of the extruder were changed as shown in Table 7, and various evaluations were performed.
[0637] [Table 6]
[0638]
[0639] [Table 7]
[0640]
[0641] (3) Example C (Example of Embodiment C of the Present Disclosure) <Evaluation Method>
[0642] <Gap between the inner wall of the barrel and the screw>
[0643] The measurement was carried out in the same manner as in Example A.
[0644] <Mixture filling ratio>
[0645] When extruding, the rotation of the screw and the supply of raw materials are suddenly stopped, the screw is pulled out, and the mixture adhering to the screw surface is collected and measured, and the volume filled with the mixture is calculated by dividing it by the density of the mixture. Then, the volume filled with the mixture is divided by the volume of the space described below to calculate the filling rate of the mixture.
[0646] <Zone length of the region where the mixed material pressure is 0.3 MPa or more / barrel inner diameter ratio>
[0647] The extruder barrel is equipped with a plurality of resin pressure gauges to monitor the resin pressure during extrusion, thereby measuring the resin pressure of each zone. The total length of the zone showing a mixed pressure of 0.3 MPa or more is divided by the barrel inner diameter to calculate.
[0648] <Space Volume Ratio>
[0649] The space volume was calculated by subtracting the screw volume (the total of the element volume and the shaft volume) from the barrel volume of the extruder, and the space volume ratio was calculated by dividing the space volume by the barrel volume.
[0650] <area length>
[0651] The total length of the screw elements constituting the dispersive mixing zone and the distributive mixing zone was taken as the zone length.
[0652] <Tensile elongation and flexural modulus of mixture and resin composition>
[0653] The obtained mixture or resin composition was molded into a multi-purpose test piece according to ISO 294-3 using an injection molding machine under conditions according to JIS K6920-2. For the multi-purpose test piece, the tensile elongation at break was measured according to ISO 527-1, and the flexural modulus was measured according to ISO 178. It should be noted that the polyamide resin changes due to moisture absorption, so it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption.
[0654] <Thixotropic Index>
[0655] The viscoelasticity of the multipurpose test piece when melted was measured under the following test conditions.
[0656] Device name: ARES G2 TA Instruments Japan Co., Ltd.
[0657] Measurement temperature: 250°C (melting point of polyamide + 25°C), 185°C (melting point of polypropylene + 25°C)
[0658] Shear rate: 1.0~40s -1
[0659] The measurement was performed using 25 mm / 40 mm parallel plates with a gap (Gap) of 1 mm.
[0660] From the measurement results at this time, the thixotropic index was calculated according to the following formula.
[0661] Thixotropic index = (shear rate 1s -1 Viscosity / shear rate 10s -1 Viscosity at 40 °C
[0662] <Property Improvement Rate per Unit Mass of Cellulose Fiber in Mixture (Flexural Modulus Improvement Rate)>
[0663] The concentration of cellulose fibers in the mixture was determined from the ratio of the feed amounts to the extruder during extrusion, and the rate of improvement in physical properties per unit mass of cellulose fibers in the mixture was calculated according to the following formula.
[0664] (Flexural modulus of mixture - Flexural modulus of base resin) / Cellulose fiber concentration (mass %)
[0665] <Charpy impact strength>
[0666] The measurement was carried out in the same manner as in Example A.
[0667] <Average fiber length, average fiber diameter and L / D of cellulose fibers used and cellulose fibers in the resin composition>
[0668] The measurement was carried out in the same manner as in Example A.
[0669] <Weight Average Molecular Weight (Mw), Number Average Molecular Weight (Mn), and Mw / Mn Ratio of Cellulose Fiber>
[0670] The measurement was carried out in the same manner as in Example A.
[0671] <Crystallinity of cellulose fibers>
[0672] In the same manner as in Example A, a porous sheet was prepared and measured.
[0673] <Average Alkali-Soluble Polysaccharide Content of Cellulose Fiber>
[0674] The measurement was carried out in the same manner as in Example A.
[0675] <Content of Particles Having a Particle Size of 50 μm or More in the Resin Composition>
[0676] The measurement was carried out in the same manner as in Example A.
[0677] <Particle Diameter of Dispersed Phase in Resin Composition>
[0678] The measurement was carried out in the same manner as in Example A.
[0679] Materials used
[0680] For the polymer, organic fiber and dispersant, the same materials as in Example A were used.
[0681] 《Mixing method》
[0682] <Extruder Screw Structure>
[0683] As shown in Table 8, screws 1 to 5 are designed and configured with zones 1 and 2. Zone 1 of screw 1 is a dispersive mixing zone, which is composed of a plurality of kneading zones, which are a combination of a kneading element composed of any one of a split-flow screw, a notched screw, a kneading disk, an eccentric multi-strip disk, and an eccentric multi-strip screw, and a retention element composed of a seal ring and / or a reverse screw. Zone 2 of screws 1 to 5 is a distributive mixing zone, and two neutral kneading disks are arranged in the barrel 11, followed by a reverse screw.
[0684] Zone 1 of the screw 2 is a distributive mixing zone designed as a combination of single and / or multiple kneading disks and single and / or multiple counter-rotating screws.
[0685] Zone 1 of screw 3 is a dispersive mixing zone, which is designed to have one more kneading zone than screw 1.
[0686] The zone length / barrel inner diameter ratio and space volume ratio of each screw are shown in Table 8.
[0687] <Mixed Operation>
[0688] [Example C1]
[0689] The preparation of a dried cellulose fiber body and the mixing of the dried cellulose fiber body and a polymer are carried out in the following steps to produce a resin composition.
[0690] (Manufacturing of Dried Cellulose Fibers)
[0691] A dispersant is added to a cellulose fiber cake (10% by weight of solid content) in an amount of 43 parts by weight relative to 100 parts by weight of cellulose solid content, and the mixture is stirred thoroughly to obtain a cellulose fiber cake mixed with a dispersant. The cake is put into a drying device as a raw material and dried at a specified shear rate, vacuum degree, and heating temperature (jacket temperature or hot air temperature). The moisture content is measured using an infrared heating moisture meter (MX-50 (manufactured by A&D)), and the time when the moisture content reaches 7% by weight or less (the solid content reaches 93% or more) is taken as the end point of drying. The conditions are as follows.
[0692] Planetary mixer (PM)
[0693] Equipment: Planetary mixer manufactured by Kodaira Manufacturing Co., Ltd. (Model: ACM-5LVT: hook type)
[0694] Conditions: The pressure was reduced to -90 kPa using a vacuum pump while stirring at 307 rpm at a jacket temperature of 60°C. Drying under reduced pressure was performed until the product temperature reached 50°C.
[0695] As the gap, the minimum distance between the hook-shaped paddle (diameter 100 mm) and the jacket was measured.
[0696] The drying time in this condition is 180 minutes.
[0697] Regarding the drying temperature, the surface temperature of the jacket was measured at three points, and the average value was taken as the drying temperature.
[0698] (Dispersion Mixing)
[0699] Polyamide 6 was fed into the extruder at 2 kg / h, and dried cellulose fibers were fed into the extruder at 2.86 kg / h (2 kg / h as cellulose), and heated and melt-kneaded in a dispersive mixing zone to obtain a dispersed mixture.
[0700] (Distribution Mix)
[0701] Polyamide 6 was added to the dispersed mixture at 4.86 kg / h by side feeding at 15.14 kg / h, and then heated and melt-kneaded in a distribution mixing zone to obtain a resin composition. The obtained resin composition was processed into pellets using a pelletizer. As extrusion characteristics, the case where the screen was clogged within 1 hour after the extruder started operating during the extrusion process was recorded as "poor" operation stability, and the case where there was no clogging was recorded as "good" operation stability.
[0702] [Examples C2 to C9, Comparative Example C1]
[0703] A resin composition was produced by the same procedure as in Example C1 except that the composition of the resin composition and the setting conditions of the extruder were changed as shown in Tables 9 and 10, and various evaluations were performed. The results are shown in Tables 9 and 10.
[0704] [Table 8]
[0705]
[0706] [Table 9]
[0707]
[0708] [Table 10]
[0709]
[0710] Industrial Applicability
[0711] The resin composition obtained by the method for producing a resin composition disclosed in the present invention can be suitably used in a wide range of applications, such as industrial machinery parts, general machinery parts, automobile, railway, vehicle, ship, and aerospace related parts, electronic and electrical parts, construction and civil engineering materials, daily necessities, sports and leisure products, casing parts for wind power generation, and container and packaging parts.
[0712] Explanation of symbols
[0713] 100, 200, 300, 400, 600, 800 extruder
[0714] 101, 201, 301 mixing area
[0715] 102, 202, 302 melting zone
[0716] N1, N2, N3 narrow gap area
[0717] D1 pressure reduction area
[0718] H1, H2, H3 high pressure area
[0719] 11, 12, 13, 14, 21, 22, 31, 32, 33, 34 other districts
[0720] 401, 601, 801 dispersion and mixing area
[0721] 402, 602, 802 allocation mixed area
[0722] 403, 404, 603, 604, 803, 804 melting zone
[0723] 411st Dispersed Mixing Zone
[0724] 42 2nd Dispersive Mixing Zone
[0725] 41a Inflow into the first dispersing and mixing zone
[0726] 41b Outflow from the first dispersive mixing zone
[0727] 42a Inflow into the second dispersing mixing zone
[0728] 42b Outflow from the second dispersive mixing zone
[0729] a1 1st component
[0730] a2 Component 2
[0731] b. Resin composition
[0732] L Barrel length direction
Claims
1. A method for producing a resin composition comprising a first component and a second component, wherein: The first component is a polymer, The second component is an organic fiber, or a combination of an organic fiber and a polymer different from the first component. The method includes a kneading step of kneading a first component and a second component using an extruder, wherein the extruder has a kneading zone including a pressure reduction zone, The pressure reduction zone is a portion where the pressure of an inflow into the pressure reduction zone is 0.5 MPa to 20 MPa, and the ratio of the pressure of an outflow from the pressure reduction zone to the pressure of the inflow into the pressure reduction zone is 0.2 or less. The content of the second component in the inflow into the pressure reduction zone is 15% by mass to 90% by mass.
2. A method for producing a resin composition comprising a first component and a second component, wherein: The first component is a polymer, The second component is an organic fiber, or a combination of an organic fiber and a polymer different from the first component. The method includes a kneading step of kneading a first component and a second component using an extruder, wherein the extruder has a kneading zone including a pressure reduction zone, The pressure reduction zone is a portion where the pressure of an inflow into the pressure reduction zone is 0.5 MPa to 20 MPa, and the ratio of the pressure of an outflow from the pressure reduction zone to the pressure of the inflow into the pressure reduction zone is 0.2 or less. In the kneading step, an additional polymer having a lower temperature than that of the mixture is added to the mixture after passing through the pressure reduction zone, and the mixture is cooled.
3. The method according to claim 1 or 2, wherein: The method includes a kneading step of kneading a first component and a second component using an extruder, wherein the extruder has a kneading zone including a plurality of narrow gap zones in which the gap between the inner wall of a barrel and a screw is 2 mm or less.
4. The method of claim 3, wherein: The organic fibers supplied to the extruder have an average fiber length of 1 μm to 10000 μm, The ratio of the gap G1 of the narrowest gap region having the smallest gap among the plurality of narrow gap regions to the average fiber length is 0.001 to 10.
5. The method of claim 3, wherein: The organic fibers supplied to the extruder are formed into particles having an average particle size of 1 μm to 10,000 μm. The ratio of the gap G1 of the narrowest gap region having the smallest gap among the plurality of narrow gap regions to the average particle diameter is 0.001 to 10.
6. The method according to claim 1 or 2, wherein: The pressure of the inflow into the pressure reduction zone is 0.5 MPa to 15 MPa.
7. The method according to claim 1 or 2, wherein: The number of the pressure reduction zones is 1 or more and 10 or less.
8. The method according to claim 1 or 2, wherein: The method includes a kneading step of kneading the first component and the second component using an extruder, wherein the extruder has a kneading zone including a plurality of high-pressure zones having a pressure of 0.1 MPa or more, The pressure P1 of the highest pressure zone having the highest pressure among the plurality of high pressure zones is greater than 0.5 MPa, and a ratio P1 / P2 of the pressure P1 to an average value P2 of the pressures of high pressure zones other than the highest pressure zone is greater than 1 and less than 100.
9. The method of claim 8, wherein: A ratio P1 / P3 of the pressure P1 to the pressure P3 of each high pressure zone other than the highest pressure zone is greater than 1 and is equal to or less than 100.
10. The method of claim 8, wherein: For each zone of the high pressure region, The pressure of the inflow into the high pressure zone is 0.5 MPa to 20 MPa, and A ratio of a pressure of an outflow from the high-pressure region to a pressure of an inflow into the high-pressure region is 0.2 or less.
11. The method of claim 8, wherein: For each of the high-pressure zones, a content of the second component in the inflow into the high-pressure zone is 15% by mass to 90% by mass.
12. The method of claim 8, wherein: In the kneading step, an additional polymer having a lower temperature than the mixture is added to the mixture after passing through all of the plurality of high-pressure zones, and the mixture is cooled.
13. The method of claim 8, wherein: The number of the high pressure areas is 2 or more and 10 or less.
14. The method of claim 8, wherein: The P1 is not less than 0.5 MPa and not more than 15 MPa.
15. The method of claim 8, wherein: The P2 is greater than or equal to 0.1 MPa and less than or equal to 10 MPa.
16. The method of claim 9, wherein: The P3 is not less than 0.1 MPa and not more than 10 MPa.
17. The method of claim 8, wherein: The P1 / P2 is greater than or equal to 2 and less than or equal to 20.
18. The method of claim 9, wherein: The P1 / P3 is greater than or equal to 1.5 and less than or equal to 50.
19. The method of claim 1 or 2, wherein: The method comprises the following steps: A dispersive mixing step of dispersing and mixing the first component and the second component in a dispersive mixing zone of an extruder to obtain a dispersive mixing product; and A distributing and mixing step of distributing and mixing at least the dispersed mixed product in a distributing and mixing zone of an extruder to obtain a resin composition, The concentration CA of the second component in the dispersive mixing zone is 10% to 90% by mass, the concentration CB of the second component in the distributive mixing zone is 1% to 50% by mass, and the ratio CA / CB is 2 to 90.
20. The method of claim 19, wherein: The method further includes, before the dispersive mixing step, a step of adding the second component to the melt of the first component to obtain a premix, and supplying the premix to the dispersive mixing zone.
21. The method of claim 1 or 2, wherein: The organic fiber is cellulose fiber.
22. The method of claim 1 or 2, wherein: The organic fibers in the resin composition have an average fiber diameter of 1000 nm or less and an average fiber length / average fiber diameter ratio of 30 or more.
23. The method of claim 1 or 2, wherein: The organic fibers are supplied to the extruder in the form of a dry body.
Citation Information
Patent Citations
Manufacture of reactor blend polyolefin and catalyst therefor
JP1985035006A
Method and catalyst for controlling polyolefin density and molecular weight
JP1985035007A
Manufacture of polyethylene having broad molecular weight distribution and catalyst therefor
JP1985035008A
Catalyst for use in closed geometric addition polymerization, its manufacture, precursor thereof, method of its use and novel polymer prepared thereby
JP1991163088A
Manufacture of polyolefin
JP1992012283B2